Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 134991943 species occurrences available in GBIF matching the query: (Query is too complex. Can be viewed on the landing page) The dataset includes 134991943 records from 13020 constituent datasets: 20 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 31413 records from University of Guam Insect Collection. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 4 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 32 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 5 records from Description of a new subspecies of Talicada nyseus (Guérin-Méneville, 1843) from Hainan, China (Lepidoptera: Lycaenidae), with notes on the genus Talicada Moore, 1881. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 23 records from Three new species of Pambolus (Braconidae: Pambolinae) from Mexico, with comments on the variation of P. oblongispina Papp. 14 records from Artenvielfalt des "Grünen Klassenzimmers". 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 66 records from Trogonoptera brookiana mollumar d’Abrera, Doggett & Parker, 1976 (Lepidoptera: Papilionidae), a subspecies or a synonym?. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 32 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 85 records from Revision of world species of the genus Oreiscelio Kieffer (Hymenoptera, Platygastroidea, Platygastridae). 31 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 2 records from First record of Orthelimaea himalayana (Ingrisch, 1990) (Orthoptera: Tettigoniidae: Phaneropterinae: Elimaeini) from India with description of its female. 4 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 2 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 22007 records from OPIE_National_2017_12_18. 1 records from A new aberrant Doryctinae genus (Hymenoptera: Braconidae) from French Guiana. 89 records from UWIZM Molluscs. 14 records from An annotated checklist of Ciidae (Coleoptera: Tenebrionoidea) of Iran. 2 records from Inventaire biodiversité du site Pierre Fabre d'Aignan. 92 records from Review of Thoreyella Spinola with the description of two new species from Brazil (Heteroptera, Pentatomidae). 3 records from Hidden diversity in European bees: Andrenaamieti sp. n., a new Alpine bee species related to Andrenabicolor (Fabricius, 1775) (Hymenoptera, Apoidea, Andrenidae). 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 4 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 29 records from The genus Chalybion Dahlbom, 1843 (Hymenoptera: Sphecidae) from Northwest Vietnam, with description of a new species. 7 records from First records of Glaresidae (Coleoptera) in China, with the description of a new species from Inner Mongolia and Shaanxi. 382 records from orthopteracollections-nhmj-ioj. 26 records from Genus Bungona Harker, 1957 (Ephemeroptera: Baetidae) from China, with descriptions of three new species and a key to Oriental species. 17 records from Notes On Claudioperla Tigrina (Klapálek) In Ecuador (Plecoptera: Gripopterygidae). 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 115 records from Diagnostic des Espaces Naturels Sensibles des Yvelines. 7 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 120 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 25 records from Collections of Bioclass, school #179, Moscow. 505 records from Données du/de la naturaliste Houpert Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 216 records from New Records of ground beetles for Colombia (Coleoptera: Carabidae). 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 718 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 282 records from Middlebury College Bee Collection. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 135 records from Brachymelecta Linsley, 1939, previously the rarest North American bee genus, was described from an aberrant specimen and is the senior synonym for Xeromelecta Linsley, 1939. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 11 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 11 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 44 records from Phytoplankton abundance in surface water during cruise Alkor 237-1. 25 records from Novas Espécies De Acrosternum Subgênero Chinavia (Heteroptera, Pentatomidae, Pentatomini). 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 34 records from The Moroccan species of Chyromyidae (Diptera) with descriptions of five new species of Aphaniosoma Becker. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 7 records from Grupo de Macroinvertebrados de la laguna Cristalina Páramo de la Rusia-Boyacá.. 24 records from Überall ist Wunderland. 100 records from INNS Data: All Taxa (West Wales). 15 records from Macrobenthos Chukchi Sea, 1986. 222 records from Taxonomic revision of the Neotropical genus Ormiophasia Townsend, 1919 (Diptera: Tachinidae), with the description of eight new species. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 83 records from Données naturalistes de Ingénieurs écologues GEREA. 2 records from Groehnaltica batophiloides, a new genus and species of flea-beetles (Coleoptera Chrysomelidae) from Baltic amber, described using X-ray microtomography. 124 records from Distribution And New Records Of Lymexylidae (Coleoptera: Lymexyloidea) In Guatemala And Mexico. 4 records from sediment metagenome Metagenome. 1 records from Taxonomy of the weevil genus Plumolepilius Barrios-Izás & Anderson (Coleoptera Curculionidae: Molytinae: Conotrachelini): new species from Central America. 24 records from A Gondwanan concept of Simplimorpha Scoble (sensu lato): a step toward clarity in the generic diagnostics of global Nepticulidae (Lepidoptera). 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 5 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 27 records from The Nymph Of Holcoperla Angularis (Wisely) (Plecoptera: Gripopterygidae) From New Zealand. 19 records from Revision of the Greater Antilles genus Paratrikona Spaeth, 1923 (Coleoptera: Chrysomelidae: Cassidinae: Dorynotini). 136 records from Données naturalistes de Marie-France LECCIA. 4 records from Faunal assemblage of sediment core TR149-31. 18 records from Naturtag. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 134 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 2181 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 73 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 115 records from Swedish Malaise Trap Project (SMTP) - Vespinae. 29 records from Review of Glaphyrosoma (Orthoptera: Stenopelmatoidea: Anostostomatidae) including new species and biological information. 2 records from Two new species of Amphinemura (Plecoptera: Nemouridae) from Tibet. 8 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 193 records from A Compendium Of Distributional Records For Oroperla Barbara Needham, 1933 (Plecoptera: Perlodidae), With Additional Documentation Of Reproductive Morphology And Biology. 4 records from Taxonomic revision of the Neotropical genus Ectophasiopsis Townsend, 1915 (Diptera: Tachinidae: Phasiinae). 31 records from Taxonomic review and distribution of the genus Vespula Thomson, 1869 (Hymenoptera: Vespidae: Vespinae) from Vietnam. 265 records from Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision. 169 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 123 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 363 records from Données du/de la naturaliste Kohn Annie provenant de la base de donnée du SINP Île-de-France CETTIA. 1839 records from Données naturalistes de la Société pour le Muséum d'Orléans et les Sciences (SOMOS). 15 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 7 records from Steinbruch Mainz-Weisenau, 4.Jahr. 12858 records from Colecção Entomológica IIA. 56 records from Colección de Zoología Universidad Icesi: Insectos. 4 records from Rediscovery of Lustrina Kurian (Hymenoptera, Chrysididae), with redescription of L. assamensis Kurian. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 12021 records from Tasmanian Natural Values Atlas. 10090 records from Macaulay Library Audio and Video Collection. 2305 records from Museu Darder de Banyoles. 3764 records from Swiss National Cicadidae Databank. 495 records from USFWS Bee surveys - Sandbar WMA, VT 2018. 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 17109 records from Lepidopterous specimens of Yamagata Prefectural Museum. 20 records from Biting midges of the tribe Ceratopogonini (Diptera: Ceratopogonidae) from the Middle East, with keys and descriptions of new species. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 53 records from Priest Pot species list, Cumbria, Britain. 6 records from Dactylobasis gen. nov. from Colombia, a new genus of Zygoptera with Teinobasini affinities (Odonata: Coenagrionidae). 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 7 records from The larva and pupa of Potamyia flavata (Banks 1934) (Trichoptera: Hydropsychidae): Description, life cycle, and notes on its biology. 20 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 2 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 1990 records from Orthoptera - SMF. 5698 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 17717 records from Observations occasionnelles Parc national des Pyrénées. 6 records from A contribution to the knowledge of Dermestidae (Coleoptera) from Guatemala. 4 records from A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae). 265 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 20 records from Macaronesian Muscidae (Diptera). I. The genus Hebecnema Schnabl with description of a new Canarian endemic species and a review of the European fauna. 2132 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 1289 records from RECORD Orthoptera Data. 4 records from hips of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species. 316 records from Orthoptera Tettigoniidae as indicators of biodiversity hotspots in the Guinean Forests of Central and West Tropical Africa. 51 records from Diversity of beetles associated with watermelon crops Citrullus lanatus (Thunb.) Mats. in the region of Ouargla (southern Algeria). 54 records from Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae). 4 records from Description of new genus and species of Ochlerini from Central America (Hemiptera: Pentatomidae: Discocephalinae) ¹. 24 records from The geometrid moths of Ethiopia I: tribes Pseudoterpnini and Comibaenini (Lepidoptera: Geometridae, Geometrinae). 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 10149 records from Bumblebees, cuckoobees and butterflies in southern Poland. 2 records from First report on Paratischeria from Asia (Lepidoptera: Tischeriidae). 3 records from New genera of Alleculinae (Coleoptera: Tenebrionidae: Alleculinae: Alleculini) from the Oriental Region. Part XI-Vietnalia gen. nov.. 6 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 6 records from Pollen and spore abundance of Hole 42-380A. 3703 records from List of animalia, fungi and plant species recorded through naturalist observations and research activities in Benin. Data mobilized in the framework of a JRS Biodiversity Foundation project of Benin. 3 records from Two new Brazilian species of Neapion Alonso-Zarazaga, 1990 subgenus Neotropion Alonso-Zarazaga, 1990 with a key to South American species (Brentidae: Apioninae). 80 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 1 records from A new species of the genus Protoplotina Miyatake (Coleoptera: Coccinellidae) from India. 1 records from Redescription of the remarkable Zhiltzovaia amabilis (Jewett, 1958) comb. nov. (Plecoptera, Perlodidae) based on types and new material from Himalaya and Pamir Mountain systems. 8276 records from MfN - Mallophaga Collection. 69 records from The coastal rove beetles (Coleoptera, Staphylinidae) of Atlantic Canada: a survey and new records. 10 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 13 records from Ichneumonid wasps from Madagascar. VI. The genus Pristomerus (Hymenoptera: Ichneumonidae: Cremastinae). 15 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 8 records from Schulteich Heinrich-Mann-Schule. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 115 records from Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae). 558 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 362 records from The genus Sphecodes Latreille 1804 (Hymenoptera: Apoidea: Halictidae) in Central Asia. 54803 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 1 records from A short taxonomic note on the katydids from the genus Cercoteratura Gorochov, 2019 (Orthoptera: Tettigoniidae: Meconematinae), with a key to species. 85 records from Bannwald Burghauser Forst. 6 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 1 records from Distributional notes on some Nosodendridae (Insecta, Coleoptera) - XXI. A new Nosodendron species from Malaysia. 25471 records from SEWBReC Bees, Wasps and Ants (South East Wales). 4 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 5 records from Oosagitta gen. nov. from tropical Africa, with revision of two species and description of four new species (Coleoptera: Chrysomelidae, Galerucinae). 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 9 records from Three new species of Lecteria Osten Sacken, 1888 (Diptera: Tipulidae) from a scientific survey in Mitaraka (French Guiana). 4 records from The first record of genus Gryllomorpha Fieber in Romania (Orthoptera: Gryllidae: Gryllomorphinae). 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 342 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 21 records from Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae). 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 6 records from Description of Cephalotes specularis n. sp. (Formicidae: Myrmicinae) - the mirror turtle ant. 77 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 5425 records from 2020_biodiversity_information_specimen. 149 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 1141 records from Données naturalistes de Quentin ROME. 2 records from Aphaenogaster gamagumayaa sp. nov.: the first troglobiotic ant from Japan (Hymenoptera: Formicidae: Myrmicinae). 262 records from SEWBReC Springtails and allies (South East Wales). 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 749 records from Carabidae of Wales and England. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 8255 records from Insect specimens of Okinawa Prefectural Museum & Art Museum. 8 records from Three new minute leaf litter beetles discovered by citizen scientists in Maliau Basin, Malaysian Borneo (Coleoptera: Leiodidae, Chrysomelidae). 32 records from Artenvielfalt auf dem Schulgelände. 5 records from Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 5 records from Two new and one newly recorded species of Polypedilum Kieffer 1912 with DNA barcodes from Oriental China (Chironomidae: Diptera). 6791 records from National Museum of Natural Science. 8421 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 27 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 142 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 73 records from Données de la structure ONEMA/AFB provenant de la base de donnée du SINP Île-de-France CETTIA. 35 records from Données de la naturaliste Laurence Beauchamp. 1614 records from New Brunswick Museum Collection. 123 records from Ladybirds of Ireland. 23 records from The world species of Ophthalmothrips Hood (Thysanoptera; Phlaeothripidae), with new records from Africa, China and Japan. 12 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 3 records from A new madicolous species of Nilotanypus Kieffer (Diptera: Chironomidae) from Amazon region, northwestern Brazil. 13544 records from Données naturalistes de Bruno OGER. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 29 records from New dark species of the bee genus Colletes (Hymenoptera, Colletidae) from Mexico and Guatemala. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 6 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 1 records from The giant “ penis ” of a newly described species in the subgenus Scotoconiopteryx from Peru (Neuroptera: Coniopterygidae: Coniopteryginae: Coniopteryx). 1 records from Norwegian Lepidoptera working group. 11 records from Taxonomic revision of Brazilian genus Tyrannoseira Bellini & Zeppelini, 2011 (Collembola, Entomobryidae, Seirinae). 16 records from Données naturalistes de ROLLAND Blandine. 338 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 2 records from Description of the female of Dicterias atrosanguinea Selys 1853, with notes on male genital ligula and male behavior (Odonata: Dicteriadidae). 55 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 13 records from Anmerkungen zur Gattung Dapsa L, 1829 (Coleoptera, Endomychidae). 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 95309 records from Paleobiology Database. 3 records from Distribution Of Moselia Infuscata (Claassen, 1923) (Plecoptera: Leuctridae) In Canada. 74 records from Taxonomy and Biogeography without frontiers – WhatsApp, Facebook and smartphone digital photography let citizen scientists in more remote localities step out of the dark. 19 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 71 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 11 records from Changes in the genus Beana Walker (Beaninae Zahiri & Holloway) with two new species and removing Beana nitida Tams to a new genus Beanoides (gen. nov.). 7 records from Thomas L. Casey and Rhode Island. 151 records from A checklist of the non-leaf-cutting fungus-growing ants (Hymenoptera, Formicidae) from Colombia, with new biogeographic records. 1 records from Sächsische Schweiz (Pfaffenstein). 108 records from Studies in Hawaiian Diptera I: New Distributional Records for Endemic Asteia (Asteiidae). 26 records from Some lesser known silent crickets (Orthoptera: Gryllidae: Euscyrtinae) from the hilly tracts of India. 4298 records from ColRest_Raw1. 3 records from A new species of Eupatorus Burmeister, 1847 related to Eupatorus birmanicus Arrow, 1908 from southwestern China (Coleoptera: Scarabaeidae: Dynastinae). 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 2 records from Two new species and ten new records of Heteroptera from Turkey, including the first record of the potential alien Campylomma miyamotoi in the Western Palaearctic. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 2 records from A contribution to the knowledge of the genera Fissocantharis Pic, 1921 and Micropodabrus Pic, 1920 from Taiwan (Coleoptera, Cantharidae). 11 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 4 records from Studies in Mexican Grasshoppers: Liladownsia fraile, a new genus and species of Dactylotini (Acrididae: Melanoplinae) and an updated molecular phylogeny of Melanoplinae. 870 records from Données du/de la naturaliste Barande Serge provenant de la base de donnée du SINP Île-de-France CETTIA. 1743 records from Updating the knowledge of the flower flies (Diptera: Syrphidae) from Chile: Illustrated catalog, extinction risk and biological notes. 60729 records from flora&fauna(NIBR)2019. 4 records from Ameisen von Madagaskar, den Comoren und Ostafrika.. 13 records from Roter Berg Werdau (Leubnitz). 1201 records from Hormigas (Hymenoptera: Formicidae) del Centro de Colecciones Biológicas de la Universidad del Magdalena. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 1 records from Cryptobiont assemblages's dataset of coral reefs using ARMS in B10 Reef and Mahahual Reef of the Great Caribbean. 3258 records from Données naturalistes de Charlotte PICARD. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 7 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 1 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Department of Plant Protection. 29737 records from University of California Santa Barbara Invertebrate Zoology Collection. 32 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 2227 records from IRAD Cameroon insect collection. 47 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 10 records from Sistema de Monitoreo de Arrecifes Coralinos - SIMAC: Abundancia de invertebrados vágiles. 1156 records from The Reduviidae (Hemiptera: Heteroptera) of Alabama, with a morphological key to species. 626 records from Etude des coléoptères de l'ENS de Voulangis (77). 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2814 records from Grand_Site_Sainte-Victoire_2017_12_18. 2 records from Vietnamella chebalingensis, a new species of the family Vietnamellidae (Ephemeroptera) from China based on morphological and molecular data. 62 records from Synopsis of Lestes from Brazil with description of Lestes demarcoi sp. nov (Zygoptera: Lestidae). 9 records from Redescription of Isotoma grana Lee, Kim & Kim, 1993 and description of a new species of Isotoma Bourlet, 1839 (Collembola: Isotomidae) from Korea. 3 records from A new species of planthopper in the genus Myxia (Hemiptera: Auchenorrhyncha Cixiidae) from the Reserva Privada el Silencio de Los Angeles Cloud Forest in Costa Rica. 74466 records from Entomology Collection at the Natural History Museum of Utah. 61 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 6 records from Mollusc specimens of Parthenon Tama History Museum (PTHM). 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 119 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 124 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (1), 2009 - Données faune. 10 records from New genus, new species and new records in Lamiinae (Coleoptera, Cerambycidae). 142 records from Hartland Nature Club Lepidoptera Collection. 404 records from Symphyla Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 36 records from Type specimens of Ichneumonidae (Hymenoptera) described by Brèthes held in the Museo Argentino de Ciencias Naturales “ Bernardino Rivadavia ”, Argentina. 245 records from A revision of Colletes Latreille (Hymenoptera: Colletidae: Colletinae) from Brazil, Paraguay and Uruguay. 745 records from UTEP Invertebrates (Arctos). 4182 records from Diptera Collection of Museum and Institute of Zoology PAS. 4 records from Taxonomy of the Myrmicine ant genus Temnothorax Mayr, 1861 (Formicidae: Myrmicinae) in the Arabian Peninsula. 11 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 107 records from Revision of the Traumatomutilla gemella species-group (Hymenoptera, Mutillidae) with the description of its hitherto unknown males. 15 records from Schulteich Freie Waldorfschule Darmstadt. 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 61 records from The Onthophagus fuscus (Coleoptera: Scarabaeidae) species complex: an update and the description of a new species. 1082 records from Données LPO Réserve naturelle régionale du marais de la Vacherie. 6 records from Nueva especie de Aleuropleurocelus Drews y Sampson (Hemiptera: Aleyrodidae) y clave para especies del grupo de forma oval. 95208 records from Western Australian Museum provider for OZCAM. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 16 records from Revision of the euryglossiform species of the Afrotropical bee genus Scrapter Lepeletier & Serville, 1828 (Hymenoptera: Apoidea: Colletidae). 19619 records from Carabidae of the Carpathians. 23 records from The Phalacridae (Coleoptera, Cucujoidea) of Canada: new records, distribution, and bionomics with a particular focus on the Atlantic Canadian fauna. 15 records from 1848-1982 Lundy Field Society The Marine Fauna of Lundy. 19 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 8 records from An overview of Scirtidae (Coleoptera) described by Antoine Joseph Jean Solier (1792 - 1851). 48702 records from NRW Regional Data: South East Wales Non-sensitive species. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 13 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from First fossil Eccoptarthridae (Coleoptera: Curculionoidea) from the Mesozoic of China. 29 records from Four new species of the subgenus Tachycines (Gymnaeta) (Rhaphidophoridae Aemodogryllinae: Aemodogryllini) from caves in northern Guizhou, China. 15 records from Review of the genus Pagastia Oliver (Diptera: Chironomidae: Diamesinae) from North America, with description of P. (P.) subletteorum sp. nov.. 1 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 1 records from University of Michigan Museum of Paleontology - Vertebrates. 99 records from Données naturalistes d'Océane ROQUINARC'H. 958 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 10 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 672 records from Colección de Entomología - Curculionidae. 9 records from Hyleina kaphetea, a new genus and species of clearwing moths from tropical Africa (Lepidoptera: Sesiidae: Sesiini). 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 81 records from Servicios ecosistémicos de polinización y zoocoria para 10 remanentes de bosque seco tropical en el Valle del Cauca. 867 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 7 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 2 records from Loneura Navás (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus. 5370511 records from International Barcode of Life project (iBOL). 2969 records from Carabidae of Mordovia State Nature Reserve. 1 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 24 records from LBV 100 - Artenvielfalt am Rothsee. 48 records from Swedish Malaise Trap Project (SMTP) - small parasitic aculeate families. 109 records from Données naturalistes de Xavier BONNET. 3 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 17443 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 60 records from Key to South American genera of Acanthocinini (Coleoptera, Cerambycidae Lamiinae) with erect setae on elytral surface. 6237 records from Plecoptera. 4 records from Flora und Fauna in unserer Kita. 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 9 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 13707 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 41 records from New Species Of Neoperla Needham And Phanoperla Banks (Plecoptera: Perlidae) From The Philippine Islands. 15 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 22 records from First record of the subfamily Brachycyrtinae (Hymenoptera, Ichneumonidae) from continental Africa, with description of three new species. 2 records from Two new aphid species of the genus Cryptomyzus Oestlund, 1922 (Hemiptera Aphididae) from Kazakhstan, and keys to apterous and alate viviparous females. 280 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 3 records from Hagneia kallea gen. and sp. nov. (Hemiptera: Fulgoromorpha: Ricaniidae) from North Vietnam. 15 records from Some finds of flora and fauna in Kharkiv region. 14 records from Re-description of Coeliccia erici Laidlaw, and the description of Coeliccia sameerae sp. nov. from Peninsular Malaysia (Odonata: Zygoptera: Platycnemididae). 82 records from Taxonomic And Distributional Notes On Perlesta Teaysia, P. Golconda, And P. Shawnee (Plecoptera: Perlidae). 24 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 8 records from Reconsideration of the apterous carventine genus Crassocoris and description of Paracrassocoris gen. nov. from China (Hemiptera: Heteroptera: Aradidae). 985 records from Bees in the UVM Zadock Thompson Zoological Collection. 5 records from NZCS Brownsberg Nature Park Monitoring. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 3105 records from Collection Mollusca SMF. 2 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleobotany National Collection (BAPb). 22 records from A description of the flea species Paractenopsyllus madagascarensis n. sp. and the female sex of Paractenopsyllus raxworthyi Duchemin & Ratovonjato, 2004 (Siphonaptera, Leptopsyllidae) from Madagascar with a key to the species of Paractenopsyllus. 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 8192 records from Données naturalistes de Benoit MARTHA. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 591 records from Alan Wormington Collection. 105 records from Colección de Entomología del Museo de Historia Natural C.J. Marinkelle. 33400 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 2 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 510 records from University of Saskatchewan. 10 records from Waldstück am Schullandheim Bad Bederkesa. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1513 records from M. Gollop Collection. 5202 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1 records from Données naturalistes d'Olivier DELZONS. 53418 records from Naturalis Biodiversity Center (NL) - Diptera. 8 records from The genus Thoradonta in Thailand (Orthoptera: Tetrigidae: Scelimeninae) with description of two new species. 3 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 6 records from Review of the enigmatic genus Boalda with transfer of pulcherrima Köhler from Nephelistis and description of two new species (Lepidoptera: Noctuidae). 1 records from A New Species Of The Genus Liophloeothrips (Thysanoptera, Phlaeothripidae) From Iran. 3 records from Notioperilitus gen. nov., a new braconid genus (Hymenoptera: Braconidae: Euphorinae) from Australia, parasitoid of adult Morabinae (Orthoptera: Eumastacidae), with remarks on the generic placement of two Afrotropical euphorine species. 159 records from Pheidole (Hymenoptera, Formicidae) of Middle American Wet Forest. 7 records from Données du naturaliste Matthieu Gouirand. 47 records from The Stonefly Genus Lednia In North America (Plecoptera: Nemouridae). 5 records from A new aquatic beetle family, Meruidae, from Venezuela (Coleoptera: Adephaga). 23 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 93 records from New records of Crabronidae fauna (Hymenoptera, Apoidea) of Tunisia. 2 records from Taxonomic notes on the genus Hydrobaenus with description of H. simferopolus sp. nov. from Crimea (Diptera: Chironomidae). 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 13482 records from Insect specimens of Rikuzen-Takata City Museum. 307 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 4 records from Re-visiting the Aphidius urticae s. str. group: re-description of Aphidius rubi Starý and A. silvaticus Starý (Hymenoptera: Braconidae: Aphidiinae). 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 18 records from A new species of Cintaroa from India and new records of Craspedophorus from Pakistan and the Philippines (Coleoptera: Carabidae: Panagaeini). 125 records from Review of the genus Meganola Dyar, 1898 (Lepidoptera: Nolidae, Nolinae) from Korea, with the description of a new species. 2 records from A new tropical montane firefly genus and species, active during winter and endemic to the southeastern Atlantic Rainforest (Coleoptera: Lampyridae). 20 records from High diversity and endemism in the genus Cautires Waterhouse, 1879 (Coleoptera: Lycidae) from the Malay mountain forests, with the descriptions of fourteen new species. 6 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 21 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 34 records from The lestevoides species group of the genus Geodromicus Redtenbacher, 1857 (Insecta: Coleoptera: Staphylinidae: Omaliinae). 205 records from Bark and Ambrosia Beetles of Vermont from Thomas H. Atkinson. 2 records from The fungus-growing ant genus Apterostigma in Dominican amber.. 146 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 83 records from Données espèces - Expertise IQE 306. 2 records from Zorotypus weiweii (Zoraptera: Zorotypidae), a new species of angel insects, from Sabah, East Malaysia. 1529 records from Données Nature 18 - Études faune 2016. 15 records from Insect Collections of Okomu National Park- Nigeria. 237602 records from University of Minnesota Insect Collection. 154 records from Heinersdorfer Sumpfwiese. 13 records from Papuacocelus papuanus n. gen., n. sp. a new Eurycanthinae from Papua New Guinea, with notes on the genus Dryococelus Gurney, 1947 and description of the egg (Phasmatodea: Phasmatidae: Eurycanthinae). 45 records from A taxonomic revision of the genus Hexarhopalus (Coleoptera, Tenebrionidae Cnodalonini) from China. 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 9 records from A new troglobitic Tychobythinus from Sicily (Coleoptera, Staphylinidae, Pselaphinae). 2 records from A new species of Isometopus from Iran (Hemiptera: Heteroptera: Miridae: Isometopinae). 4 records from (Table A-2.1 to A-2.7) Abundance of macrobenthos in surface sediments in the Arctic Ocean. 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 14 records from Coleoptera identified from the Hornchurch Marshes site, Dagenham, London. 26 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 39 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 2 records from Naturschutzgebiet Müchelholz (Mücheln). 140 records from Algae of the Recherche Archipelago , Western Australia (2002-2003). 23 records from Wiese am Waldrand (Gurtweil). 186 records from Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species. 4 records from Coeliccia lecongcoi sp. nov., a new damselfly from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae). 61 records from Gastropod Specimens of the Yamagata Prefectural Museum. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 2 records from A new species of the subgenus Duolandrevus (Eulandrevus) Kirby, 1906 from Guangxi, China (Orthoptera: Gryllidae: Landrevinae). 279 records from Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 22 records from Liether Park (LMS), 5a. 2 records from Review of the species of Anastatus (Hymenoptera: Eupelmidae) known from China, with description of two new species with brachypterous females. 2736 records from Midden-Limburg Fish Ponds Survey. 5 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 8 records from Two new species of Psyttalia Walker (Hymenoptera, Braconidae, Opiinae) reared from fruit-infesting tephritid (Diptera) hosts in Kenya. 366 records from National System of Protected Areas in Poland - Animals. 2 records from Leiner-Herbar Konstanz. 13 records from New species, redescriptions and a new combination of Acanthocyrtus Handschin, 1925 and Amazhomidia Cipola & Bellini, 2016 (Collembola, Entomobryidae, Entomobryinae). 4 records from A new species of the ant genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae) from the Caribbean region. 8954 records from RNF - Données de la Communauté de Communes de Gevrey Chambertin. 895 records from Geometridae de France métropolitaine. 105 records from bmhs_moth_collection. 144 records from Cactophilic Drosophila and Opuntia. 20 records from A revision of the genus Navasoleon Banks (Neuroptera: Myrmeleontidae: Nemoleontini). 4 records from Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae). 232 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 4193 records from Leicestershire and Rutland Aculeate Records. 23 records from New and interesting species of the genus Bryaxis Kugelann, 1794 (Coleoptera, Staphylinidae, Pselaphinae) from Croatia. 16618 records from Suivi Temporel des Libellules (STELI). 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 237 records from Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae). 6 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 79 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 3 records from DFO Zoobenthos data from upper Frobisher Bay, 1967 to 1973. 12 records from Two new species of Rhiginia Stål, 1859, with taxonomical notes on species in the “ cruciata-group ” of this genus and an updated key to the New World genera of Ectrichodiinae (Heteroptera, Reduviidae). 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 70 records from Ensemble des données Orthoptères. 2185 records from The bees of Lebanon (Hymenoptera: Apoidea: Anthophila). 4347 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 5 records from Pollen profile RAC20, Lake Racou, France. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 4 records from A new species of the genus Cyrtonion (Coleoptera: Hydrophilidae: Megasternini) from the Democratic Republic of the Congo. 3 records from Some new brachypterous cockroaches (Blattodea: Blaberidae: Epilamprinae) from the Philippines. 9150 records from NEON Biorepository Carabid Collection (DNA Extracts). 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 24 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 28 records from Données naturalistes de Franck MERLIER. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 7 records from (Table 4) New palynological record of sediments from Odderade. 3 records from Protist Diversity in the East China Sea. 2 records from Two new species of the genus Malayepipona Giordani Soika (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with updated key to all recognised species. 8 records from Données espèces - Expertise IPE 79. 70 records from COLETA - IMAR/DOP-Uac reference collection from 1977 to 2012. 1010530 records from NBIS Records to December 2016. 64 records from Carrion beetles (Coleoptera, Silphidae) of Volga-Kama Nature Reserve. 172 records from Nezara viridula records held by the Royal Horticultural Society. 89 records from Rohrmeistereiplateau und angrenzendes Gebiet. 9 records from Two new species and records of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae) from southeastern China. 4 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. 1 records from Thraulodes marianoi sp. nov., a remarkable new species of mayfly (Ephemeroptera Leptophlebiidae) with dark wings from the southern Brazilian Atlantic Forest. 1719 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 28 records from Some new species of Phaneroptera, Eulioptera and Scolocerca (Orthoptera Tettigoniidae: Phaneropterinae) from West Tropical Africa. 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 44 records from Revision and phylogeny of Hypotelus Erichson: a Neotropical genus of minute rove beetles (Coleoptera, Staphylinidae, Piestinae). 4 records from The genus Aivalykus Nixon, 1938 (Hymenoptera: Braconidae: Doryctinae) with description of a new species from India and Arabian Peninsula. 108 records from Mollusca specimens of Ryukyu University Museum (Fujukan). 4 records from AMNH Bird Collection. 23643 records from CNIN/Abejas de México/Apoidea. 21 records from New species of Phaloria (Orthoptera: Phalangopsidae: Phaloriinae) from West Papua (Indonesia). 2713 records from Données du/de la naturaliste Chevallier Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Evidence for the continued presence in New Zealand of Homotrysis macleayi (Borchmann, 1909) (Coleoptera: Tenebrionidae: Alleculinae). 876 records from Ensemble des données Odonates. 2134 records from Kurzflügler_Raw1. 11 records from Notes on Catulona Rolston, 1992, and the description of a new species from Brazil (Hemiptera, Pentatomidae, Discocephalinae). 2 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 6 records from Redescriptions of three species of Pulvinaria (Hemiptera: Coccomorpha: Coccidae) in Japan. 47 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 527 records from BioBlitz Barcelona 2010-14. 18 records from Six new species of the genus Nazeris (Coleoptera, Staphylinidae, Paederinae) from China. 43 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 4 records from Art´n Vielfalt im Kinderwald. 294 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 23 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 21 records from Revision of the species related to Lalagetes subfasciatus Boheman and transfer of remaining Lalagetes species to other genera of Embrithini (Coleoptera: Curculionidae: Entiminae). 27 records from Bemerkenswerte Faltenwespen aus der äthiopischen Region. Teil 14 (Hymenoptera, Vespidae, Eumeninae). 276498 records from hymenoptera. 322 records from FFH-Gebiet "Calwer Heckengäu". 69 records from Naturalis Biodiversity Center (NL) - Crustacea. 12147 records from Danish Ants (Formicidae). 3 records from A new species, a new combination, and a new record of Crossotarsus Chapuis, 1865 (Coleoptera, Curculionidae, Platypodinae) from China. 139 records from Revision of the subgenus Stigmatophorella of Chalcophorella (Coleoptera: Buprestidae: Chrysochroinae). 27 records from Partial revision of the genus Robinsonia Grote 1866: description of five new species for the Neotropical fauna (Lepidoptera, Erebidae, Arctiinae, Phaegopterina). 55 records from The Genus Daspletis Loew, 1858 And The Description Of Two New Genera, Anasillomos And Remotomyia (Diptera: Asilidae: Stenopogoninae). 1 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 81532 records from Bob Merritt Coleoptera Dataset. 22 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 13 records from New records of mosquitoes (Diptera: Culicidae) found in phytotelmata in Northern Argentina. 8 records from Component analysis of TV-guided grab sampler GeoB10071-5. 13768 records from Mise en place d'un suivi scientifique des rhopalocères pour la production d’indicateurs de biodiversité. 70 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 7 records from Contribution to the Mesochorinae (Hymenoptera, Ichneumonidae) of Nepal. 216321 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 18472 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 1 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 31 records from Two new species of the genus Narcotica Sugi, 1982 (Lepidoptera: Noctuidae: Acronictinae). 649 records from Beetles from nature reserves and nearby forests in Østmarka. 40 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera Oecophoridae) V. The unistriatella species group, with descriptions of seven new species. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 3933 records from The Broward College Insect Collection. 28 records from Systematic Notes On Kiotina Klapálek And Hemacroneuria Enderlein (Plecoptera: Perlidae), With Description Of Four New Species. 1 records from Redescription of Leptogyra bujnitzkii (Gorbunov, 1946) comb. nov., the first representative of the gastropod subclass Neomphaliones from the high Arctic. 11 records from Supplementary Illustrations For Two Nemoura (Plecoptera: Nemouridae) Species. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 12 records from Isoperla Umpqua A New Species Of Western Nearctic Stonefly (Plecoptera: Isoperlinae). 19 records from Distribution Data for Megachile chomskyi. 175 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 47 records from Schwanseepark (87645 Schwangau). 54 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 3 records from A new species of Xiphogramma Nowicki (Hymenoptera: Chalcidoidea) from Saudi Arabia. 15 records from A review of the Blaesiina (Coleoptera, Scarabaeidae, Cetoniinae, Gymnetini). 2933 records from Ecosphère_2017_12_18. 3 records from Cuccodorodes gen. nov., an apterous Batrisitae from the tropical Himalayas (Coleoptera: Staphylinidae: Pselaphinae). 30 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 114 records from Fermanagh Flora. 9 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 2 records from On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China. 37 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 101 records from STERF 2014/2015 Hasparren (64) par l'association EcoGIS. 5 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 1037 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 2 records from Neotype Designation for Aedes (Stegomyia) albopictus (Skuse). 5 records from On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini). 509 records from Données du naturaliste Julien Birard provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Additional Characters In Perlesta Baumanni Stark (Plecoptera: Perlidae), With Notes On Other Ouachita Mountain Species. 4 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 10 records from Bees of the family Halictidae Thomson, 1869 from Dominica, Lesser Antilles (Hymenoptera: Apoidea). 14 records from Streuobstwiese Stedar 2009. 145 records from Revision of Telothyria van der Wulp (Diptera: Tachinidae) and twenty-five new species from Area de Conservación Guanacaste in northwestern Costa Rica with a key to Mesoamerican species. 155 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 6 records from New Species of Neotibilis Grazia & Barcellos (Hemiptera: Pentatomidae: Pentatomini). 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 407 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 2 records from Two new species of Batoctenus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from French Guiana. 2 records from CM Vertebrate Paleontology Collection. 1 records from Die Bachspezies 2008/2009. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 13 records from Two new species and a key to the dustywings of Mexico (Neuroptera, Coniopterygidae). 22 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 81 records from Diura Washingtoniana (Hanson) Resurrected From Synonymy With D. Nanseni (Kempny) (Plecoptera: Perlodidae), Supplemented With A Description Of The Larva And Egg And Comparison To Other Congeners. 4 records from Haematophagous biting midges of the extant genus Culicoides Latreille (Diptera: Ceratopogonidae) evolved during the mid-Cretaceous. 10179 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 5 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 2 records from Contribution to the knowledge of Himalayan and North Indian species of Scaphidium (Coleoptera, Staphylinidae). 2 records from Streuobstwiese. 789 records from Occurrence of insect species along Loduare - Golini Road, Ngorongoro Conservation Area, Arusha, Tanzania. 1 records from South American Antarctic Marine Biodiversity Literature. 6 records from Description of Lacon mertliki sp. nov. (Coleoptera: Elateridae: Agrypninae) from the Hyrcanian forest ecoregion, with a key to the Lacon species of Iran. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 15 records from Université Pédagogique Nationale de Kinshasa- Les Insectes Comestibles de la R.D. Congo (Entomophagie). Projet CABIN (Central African Biodiversity Information Network). 32 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 31 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 8 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 14 records from Species of Prioninae, Parandrinae, Lepturinae (Insecta, Coleoptera, Cerambycidae) and Disteniidae (Insecta, Coleoptera) from east Paraná State (Brazil), with three new geographic distribution records. 3 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 237 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Bioacoustics and morphology of a new bush-cricket species of the genus Isophya (Orthoptera: Phaneropterinae) from Turkey. 8 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 41 records from A new species of the genus Watsonidia Toulgoët, 1981 (Lepidoptera, Erebidae, Arctiini): example of polymorphism in the Amazon of Peru. 3 records from Description of a new species of the genus Maua Distant (Hemiptera, Cicadidae) from China. 13 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from A new species of Marsipococcus Cockerell & Bueker (Hemiptera: Coccomorpha: Coccidae) from Malaysia. 6 records from A new Dondice Marcus Er. 1958 (Gastropoda: Nudibranchia) from the Mediterranean Sea reveals interesting insights into the phylogenetic history of a group of Facelinidae taxa. 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 1 records from Pritchardia boliviensis N. Gen., N. Sp. (Anoplocephalidae: Linstowinae) a tapeworm from opossums (Didelphidae) in the yungas and lowlands of Bolivia and Atlantic forest of Paraguay. 6 records from Three new species of trigonopoid Platynotina (Tenebrionidae: Pedinini) from the Baviaanskloof Nature Reserve, South Africa. 8338 records from NE Scotland other invertebrate records 1800-2010. 332 records from Colección de chinches (Insecta: Hemiptera) del Centro de Colecciones Biológicas de la Universidad del Magdalena. 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 11791 records from Datos de ocurrencia de triatominos americanos del Laboratorio de Triatominos del CEPAVE (CONICET-UNLP). 34 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 14867 records from RNF - Données du Conservatoire d'espaces naturel Franche-Comté. 13 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 6 records from Deep-sea meiobenthos at Calvi (Corsica) sampled in September 1982. 98 records from Données opportunistes sur les odonates. 28 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1 records from A new species of the genus Nenasa (Hemiptera: Fulgoroidea: Caliscelidae) from mainland China. 17 records from Census of animals species through Benin from 2011 to 2019. 1063 records from Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée via les portails gérés par la LPO de 2013 à 2017. 34 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 12 records from 2017 Onwards Rare Invertebrates in the Cairngorms Shining Guest Ant Survey Data. 16742 records from Données Entomologiques A. HORELLOU 1988-2018. 77 records from The Pyraloidea (Lepidoptera) fauna of the woody savannah belt in Mali, West Africa. 163 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from A new micropterous winter species of Leuctra (Plecoptera: Leuctridae) and little known endemic stoneflies from the Greater Caucasus. 12 records from Rediscovery of Glenurus incalis Banks (Neuroptera: Myrmeleontidae), and notes on the Brazilian species of Glenurus Hagen. 1 records from Geführte Wanderung im Eselsbachtal. 6 records from A new species of Hygrogeus Mulsant & Rey, 1880 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) from Xizang, China. 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 31 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 14 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 256 records from EDIT - ATBI in Gemer area (Slovakia). 22137 records from Global compendium of Aedes albopictus occurrence. 4 records from Inventaire malacologique de la RNR des Marais de Stors. 1 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 28 records from Teich Berlin Wuhlheide. 56 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 7 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 4 records from AKG-Gelände (Bensheim). 24 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 10 records from Taxonomic and nomenclatural changes in three species of Pterostichus Bonelli (Coleoptera: Carabidae) from the Far East. 3 records from Cyana barbora, a new species from Sichuan, southwestern China (Lepidoptera Erebidae, Arctiinae, Lithosiini). 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 2 records from Taxonomy of the Oriental leafhopper genus Parabolopona (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with a new species from China. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 43 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 77 records from Shannon Index and species richness for arthropods. 50 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 3 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 1 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 10699 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 39 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 4 records from Two new genera for the Botyodes species complex (Lepidoptera: Pyraloidea: Crambidae). 84 records from Revision of Scelio pulchripennis - group species (Hymenoptera, Platygastroidea, Platygastridae). 81 records from Revisão Do Gênero Runibia (Heteroptera, Pentatomidae, Pentatomini). 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 5 records from The genus Eremiothrips (Thysanoptera: Thripidae) from China, with one new species. 25589 records from Liste des insectes associés au Vitellaria paradoxa C. E Gaertner, au Centre et au Nord du Bénin. 1 records from Descriptions of new Genera and Species of Odonata in the Collection of the British Museum, chiefly from Africa.. 33 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 9120 records from ICEL (Land - Invertebrates). 5 records from Discovery of the genus Micropeneta Pic in China, with description of a new species (Coleoptera: Tenebrionidae: Gnathidiini). 107 records from Revision of the genus Miridiba Reitter, 1902 (Coleoptera, Scarabaeidae, Melolonthinae): genital morphotypes and new taxonomic data. 245 records from A review of Tersilochinae (Hymenoptera: Ichneumonidae) of Finland. Part 1: taxonomy. 1 records from Biological Reference Collections ICM-CSIC. 22 records from Review of Aphidiinae parasitoids (Hymenoptera: Braconidae) of the Middle East and North Africa: key to species and host associations. 6 records from First Record of Dericorys albidula Serville, 1838 (Orthoptera: Dericorythidae) in Tunisia and Libya. 4 records from Maritimes 4VSW Research Vessel Surveys. 939 records from Coléoptères Silphidés du département du Loiret. 310 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 8 records from Revision of the Western Palae arctic species of the genus Casinaria H (Hymenoptera, Ichneumonidae, Campopleginae). 244 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 35 records from Revision of the genus Neozavrelia Goetghebuer, Thienemann, 1941 (Diptera Chironomidae) from Eastern Siberia and the Russian Far East, with the description of new species. 51 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 2 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 129 records from Species of the bee genus Centris Fabricius, 1804 described by Heinrich Friese (Hymenoptera: Apidae). 6 records from A revision of the genus Zyras (Zyras) Stephens, 1835 (Coleoptera, Staphylinidae, Aleocharinae). I. Current classification status and the redefinition of the genus. 12 records from Three new cave species of the subgenus Tachycines (Gymnaeta) (Orthoptera Rhaphidophoridae: Aemodogryllinae) from northern Guizhou, China. 12 records from Description of a new Aemene Walker, 1854 from North Thailand and Myanmar, with a checklist of the genus (Lepidoptera, Erebidae, Arctiinae). 3 records from Review of Campsicnemus species from the Atlantic Ocean Islands (Diptera: Dolichopodidae). 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 11 records from Revision of the Ulopinae leafhoppers (Hemiptera: Cicadellidae) of the Indian subcontinent, I. Ulopini genera: Daimachus, Radhades and Ulopsina. 17 records from Morphology and DNA barcodes of two species of Bradysia Winnertz from China (Diptera, Sciaridae), with the description of Bradysia minorlobus Yang, Shi & Huang sp. n.. 4 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 4 records from Description of a new Oriental stonefly species, Phanoperla constanspina (Plecoptera: Perlidae) from Mindanao, Philippines and association of life stages using DNA barcoding. 1 records from Occurrence data of some marine invertebrates and freshwater crabs housed in the natural history collection at the National Museums of Kenya. 8 records from Two remarkable new species of Argyrophorus Blanchard from the Peruvian high Andes (Lepidoptera, Nymphalidae, Satyrinae). 1 records from MSB Fish Collection (Arctos). 5 records from A New Species of Abbrosoga (Hemiptera: Fulgoroidea: Delphacidae), An Endemic Puerto Rican Planthopper Genus, with an Updated Checklist of the Delphacidae of Puerto Rico. 13 records from A contribution to the taxonomy of Anthaxia (Cratomerus) (Coleoptera Buprestidae: Anthaxiini) of East Africa. 66 records from Langes Tannen (Uetersen). 121 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 5 records from Reduced antennal segmentation in a new species from Iran of the genus Aeolothrips (Thysanoptera: Aeolothripidae). 52 records from Churchyards for London. 553 records from Biodiversity of the scentless plant bugs (Hemiptera: Rhopalidae) in southern South America. 1 records from Key to genera of Chinese Coelidiinae leafhoppers, with description a new species of the leafhopper genus Baseprocessa (Hemiptera: Auchenorrhyncha: Cicadellidae). 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 79 records from Etude d'impact projet cluster des médias Jeux Olympiques. 1 records from Aktion des Romain-Rolland-Gymnasiums. 1 records from Natura 2000 Vallée de la Seille. 24 records from Survey data of tidal flats on the Monitoring sites 1000 project, BDCJ. 10898 records from Inventario de Hymenóptera; parasítica en México. 3 records from A new species of the genus Cyparium from northern Sulawesi, Indonesia (Coleoptera: Staphylinidae: Scaphidiinae). 174 records from Etude naturaliste des landes et pelouses à Fulchiron, Maisse (91). 9 records from New species of the cicada genus Semia Matsumura (Hemiptera: Cicadidae) from China and a phylogeny of Semia spp. and their relatives based on molecular data. 72 records from MfN - Fossil Fish Collection. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 8277 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1034 records from Données de la structure ANCA (les Amis Naturalistes des Coteaux d'Avron) provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Caroperla brevihamata (Plecoptera: Perlidae), a new stonefly species from Guangxi Zhuang Autonomous Region of southern China. 81 records from Jeu de données de la Société limousine d'Etude des Mollusques. 53 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 4 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 26 records from schulgarten. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 3 records from Données naturalistes de THÉVENOT Jessica. 2 records from Trends of karyotype evolution in the Neotropical long-legged crickets Phalangopsidae (Orthoptera, Grylloidea). 127 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 817 records from Lucanidae. 81 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 13 records from Synonymies, new records, and new species in Cerambycinae (Coleoptera Cerambycidae). 265955 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 3 records from One new species of the subgenus Xizicus (Zangxizicus) (Orthoptera: Tettigoniidae: Meconematinae) from China. 10 records from Données du naturaliste JAPIOT Xavier provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1775 records from TWIC Biodiversity Field Trip Data (1995-present). 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 2 records from Three endemic Aphaenogaster from the Siculo-Maltese archipelago and the Italian Peninsula: part of a hitherto unrecognized species group from the Maghreb? (Hymenoptera: Formicidae: Myrmicinae). 2 records from Oberes Schindelbachtal. 84 records from SNH Invertebrate Site Condition Monitoring 2015: Dunhog Moss SSSI. 12 records from Myopa nebulosa sp. nov. and Myopa bozinovici sp. nov. (Diptera: Conopidae): New thick-headed flies from a threatened biodiversity hotspot in central Chile. 101 records from Epiproct And Dorsal Process Structure In The Allocapnia Forbesi Frison, A. Pygmaea (Burmeister), And A. Rickeri Frison Species Groups (Plecoptera: Capniidae), And Inclusion Of A. Minima (Newport) In A New Species Group. 1 records from Genebank, National Institute of Agrobiological Sciences. 8 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 8 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 10933 records from River Biologists' Database (EPA). 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 1 records from Description of a new genus and species of Hemisphaeriini from Brunei with an identification key to the Bornean species of the tribe (Hemiptera: Fulgoroidea: Issidae). 1 records from Great Eastern Ranges - Slopes to Summit. 97825 records from Tiroler Landesmuseum Ferdinandeum. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 12 records from New or rare Madagascar tiger beetles- 20. Pogonostoma (Bathypogonum) horimichioi sp. nov. and supplemented characters of P. (B) levigatum levigatum (W. Horn) and P. (B.) levigatum lucens Rivalier (Coleoptera: Cicindelidae). 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 5583 records from Données faune Nature 18 - 2017. 3 records from Hydaticus (Prodaticus) hauthi sp. nov., a new diving beetle from the cloud forest in the Cordillera El Sira, Peru (Coleoptera: Dytiscidae). 1 records from Benthic macrofauna abundance of sediment core 13077-063. 8851 records from Odonata records from RSPB Reserves 1970-2009. 24 records from Taxonomic revision of Australian Amobia Robineau-Desvoidy, 1830 (Sarcophagidae: Miltogramminae): integrating morphology and genetics finds a new species and tackles old problems. 18 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from Peyerimhoffia jaschhoforum (Diptera, Sciaridae), a new deadwood inhabiting species from Canada. 2 records from The first Cacomorphocerus species (Coleoptera, Cantharidae) from Rovno amber a second species of the genus with 11 - segmented antennae. 6 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 26 records from Four new species of Psychomyia (Trichoptera: Psychomyiidae) from China, with re-descriptions of two species. 36 records from The Trichoptera of Panama XIII. Further new country records for caddisflies (Insecta: Trichoptera) from the Republic of Panama. 1 records from Description of a new species of Megischus Brulle (Hymenoptera, Stephanidae), with a key to the species from China. 14 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 1169 records from Edible Insects Collection of the Natural History Museum Bulawayo (NMZB), Zimbabwe Occurrence dataset. 50 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1298 records from Vermont Orthoptera Records from Historic Dot Maps. 19 records from A new species and new records of Oocyclus Sharp, 1882 (Coleoptera: Hydrophilidae) from Brazil. 55 records from Integrative taxonomy of Thalerosphyrus Eatonı 1881 (Ephemeropteraı Heptageniidae) in Thailand. 1 records from Wairambar Rainforest Species list 2018. 1 records from Colección de Bacterias del Museo de Historia Natural Marina de Colombia – Makuriwa (Invemar). 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 5 records from A new species of Ashlockobius (Heteroptera: Rhyparochromidae: Myodochini) from Venezuela. 1 records from Diagnosies provisoires de quelques espèces nouvelles de fourmis de Madagascar, récoltées par M. Grandidier.. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 137 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 17 records from Description of Brachymeria philornisae sp. n. (Hymenoptera: Chalcididae), a parasitoid of the bird parasite Philornis trinitensis (Diptera: Muscidae) in Tobago, with a review of the sibling species. 21 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 18 records from Naturgrundstück (Eutin). 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 1877 records from Odonata de la huasteca potosina (insecta). 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 2 records from Studies on the systematics and taxonomy of the genus Hylaeus F. (8) Revision of the Afrotropic subgenus Hylaeus (Deranchylaeus) Bridwell (Hymenoptera: Anthophila, Colletidae). 13 records from The myth of monophagy in Paralobesia (Lepidoptera: Tortricidae)? A new species feeding on Cypripedium reginae (Orchidaceae). 22 records from A new species and four new records of Diduga Moore (Lepidoptera, Erebidae Arctiinae) from Thailand. 1 records from The Little Harlequin Katydid-a new species of Paraxiphidium Redtenbacher, 1891 (Orthoptera: Tettigoniidae: Conocephalinae; Conocephalini) from the Amazonian Rainforest. 3 records from Zoology in the Middle East. 4 records from Two new species of Parandrinae (Coleoptera: Cerambycidae) in the genera Parandra and Acutandra from South America. 93 records from Données naturalistes de Mr MONTAGNER Sylvain. 12 records from Neoplasta Coquillett (Diptera: Empididae: Hemerodromiinae) from Brazil: new species and male description of N. fortiseta Smith. 159 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 21937 records from Données de l'Observatoire de la Faune de Bourgogne. 1 records from First description of the male of Oxythrips tristis Bagnall (Thysanoptera: Thripidae). 10 records from Echinodera (Ruteria) soumasi sp. n. from Greece (Coleoptera, Curculionidae). 82 records from Osmiine bees of the genus Haetosmia (Megachilidae, Osmiini): biology, taxonomy and key to species. 60 records from Ephemeroptera from the Venezuelan Guayanas´s Uplands: Families Leptophlebiidae, Euthyplociidae and Oligoneuriidae. 93 records from Descriptions of two new species of Brachyzapus Gauld & Dubois (Hymenoptera: Ichneumonidae: Pimplinae) from South Korea with key to a Palaearctic species. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 1 records from Developmental Biology among Corbiculate Bees: Bombus impatiens, Including Observations on Its Egg Eclosion. 193 records from Données du partenariat Imerys - UMS PatriNat - 2018-2020. 16 records from Cryptic diversity in the Azorean beetle genus Tarphius Erichson, 1845 (Coleoptera: Zopheridae): An integrative taxonomic approach with description of four new species. 21 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 1 records from First record of family Dipsocoridae (Hemiptera: Heteroptera: Dipsocoromorpha) from the Korean Peninsula and a new generic combination for Cryptostemma japonicum Miyamoto. 1 records from Allan Herbarium (CHR). 368 records from Biological Recording in Scotland - Bumblebee Survey. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/562-1. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 14346 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 216 records from Mission ONF 2008 d'inventaire de la Réserve naturelle de la Trinité. 28 records from Birkenloh. 51 records from Species observations during citizen science expeditions. 21 records from Nomenclatural changes and lectotype designations in the seed-beetle genus Sennius Bridwell: with the synonymization of Megasennius Whitehead & Kingsolver (Coleoptera: Chrysomelidae: Bruchinae). 1480 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 15157 records from Coleção Entomológica Moure e Costa. 8 records from The InBIO Barcoding Initiative Database: Ypsolopha rhinolophi sp. nov. (Lepidoptera: Ypsolophidae), a new species from Portugal and France unveiled by bats. 94 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 13 records from Taxonomic notes on genus Coelotrypes Bezzi (Diptera: Tephritidae: Trypetinae) with description of two new species. 2 records from A new species of Aegidium Arrow (Coleoptera: Scarabaeidae: Orphninae) from Colombia. 2 records from A new species of the subgenus Tachycines (Tachycines) (Othoptera: Rhaphidophoridae) from Guizhou, China. 2 records from Collection Cnidaria fossil SMF. 87 records from NSG Karwendel. 7 records from New Species Of Tyloperla (Plecoptera: Perlidae) From Vietnam And Thailand. 1036 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 238 records from Données naturalistes d'Olivier LAURENT. 7 records from Revision of the Afrotropical genus Susua Lugo-Ortiz & McCafferty 1998 (Ephemeroptera: Baetidae: Protopatellata). 13 records from Coleção de Coleoptera da Universidade de Brasília. 647 records from Twenty-two new species in the genus Hyphantrophaga Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, with a key to the species of Mesoamerica. 140 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 1 records from The immature stages of Phylloicus obliquus Navás, 1931 (Insecta: Trichoptera: Calamoceratidae). 22 records from Site Condition Monitoring of dragonflies on Loch aí Mhuilinn SSSI potential extension - 2016. 7 records from A new genus of the mite family Scutacaridae (Acari: Heterostigmata) associated with Trinervitermes trinervoides (Isoptera: Termitidae) from South Africa. 24 records from Données naturalistes de DUNESME Caroline. 2 records from The first record of the family Chloroperlidae (Plecoptera) from the Guangxi Zhuang Autonomous Region of southern China, with description of a new species of Sweltsa Ricker, 1943. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 3 records from Wuhle - Brücke / B1. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 1187 records from National Benthic Inventory. 1 records from A new species of the genus Humphaplotropis from China (Orthoptera: Pamphagidae, Pamphaginae). 22 records from On the taxonomy of the subgenera Cyabarda Karisch, 2013, Idiovulpecula Karisch, 2013 and Paravulpeculella Karisch, 2013 of the genus Cyana Walker, 1854, with descriptions of three new species from Africa (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 18 records from Exotic speciments butterflies at Museum Zoologi Bogor, Indonesia. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 311 records from Fiocruz/CAVAISC - Coleção de Artrópodes Vetores Ápteros de Importância em Saúde das Comunidades. 14 records from The arctic and alpine bumblebees of the subgenus Alpinobombus revised from integrative assessment of species’ gene coalescents and morphology (Hymenoptera, Apidae, Bombus). 28 records from Biodiversité marine de l’île de La Réunion. Programme BIOLAVE. 243384 records from Odonata Central. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 1037 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 3 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 33 records from Description of Coeliccia lephuocdieui sp. nov. from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae) with notes on its congeners. 10 records from Revision of Afrotropical species of the Philonthus peripateticus species group (Coleoptera: Staphylinidae: Philonthina). 2 records from Studien zur Systematik und Taxonomie der Gattung Hylaeus F. (4) Hylaeus sinensis sp. n. - Nachweis der montan-disjunkten Verbreitung einer Artengruppe um Hylaeus niger B (Apidae, Colletinae). 10 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 60 records from Seasearch Marine Surveys in the Isle of Man. 1 records from CBCGDF CCAfa Volunteer Observation Archive. 21 records from DSMZ Bacteria. 254654 records from CAS Entomology (ENT). 43 records from Pelmatellus Amicorum Delgado And Ruiz-Tapiador (Coleoptera: Carabidae), A New Species From The Andean Altiplano Of Peru. 14 records from Review of Reuteria Puton, 1875 (Heteroptera: Miridae) species present in Lodos Entomological Museum, Turkey (LEMT). 69024 records from Carnet B Lorraine. 10 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 1151 records from Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 1 records from A new species of genus Oxytauchira from India (Orthoptera: Acrididae). 228 records from MoJ BioBlitz August 2018. 5 records from Owere Fiddel. 46 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 142 records from Ensemble des données. 56 records from Données de la Réserve Naturelle Régionale du Marais de Larchant provenant de la base de donnée du SINP Île-de-France CETTIA. 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 5 records from Four new Oriental species of the ‘ Cephennomicrus group’ (Coleoptera: Staphylinidae: Scydmaeninae). 61 records from AGIR_Ecologique_2017_12_18. 79 records from Catalogue of the Syrphidae of Egypt (Diptera). 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 33 records from Données naturalistes de Nicolas LOEUILLE. 6244 records from Field Museum of Natural History (Geology) Fossil Invertebrates Collection. 52608 records from Insects, Outer Hebrides. 13 records from A new species and a key to world species of the flavipes species-group of the genus Cotesia Cameron, 1891 (Hymenoptera: Braconidae: Microgastrinae) from Japan. 2 records from A New Genus And Species Of Panaphantina (Coleoptera: Staphylinidae: Pselaphinae: Euplectitae: Trichonychini) From Australia. 8 records from Description of eight new species of the traumatically inseminating plant bug genus Coridromius (Heteroptera: Miridae: Orthotylinae: Coridromini). 43 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 16 records from An der Ohm, (Wettsaasen). 1 records from Philippine Mollusk Symbiont - ICBG Collection. 185 records from Inventaire des odonates d'intérêt communautaire. 5 records from New species of the snakefly genus Mongoloraphidia (Raphidioptera: Raphidiidae) from China. 6 records from The Lanternfly genus Polydictya (Hemiptera: Fulgoromorpha: Fulgoridae) from Sulawesi and neighbouring islands, with the description of three new species. 2112 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 11 records from New Cryptophagus H, 1792 (Coleoptera: Cryptophagidae) from Arizona (United States of America). 27 records from Taxonomic study of the genus Promalactis Meyrick (Lepidoptera, Oecophoridae) from Hainan Island, China (III). 1798 records from Insect (KIDR-IN). 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 25 records from Review the bamboo-feeding genus Arcofaciella Fennah, 1956 (Hemiptera: Fulgoromorpha: Delphacidae) with description of a new species from India. 27 records from An annotated checklist and key to the Bulgarian cockroaches (Dictyoptera: Blattodea). 7 records from Invertebrates (except insects), Outer Hebrides. 2 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 4 records from Critical Checklist of the Indian species of Hypogastrura (Collembola: Hypogastruridae) with a description of a new species from Satkosia Wild Life Sanctuary. 19 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 8177 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 94 records from Revision of the Agrilus purpurifrons species-group (Coleoptera, Buprestidae, Agrilinae). 6 records from Eulepida mbala, a new species from Zambia (Coleoptera: Scarabaeidae: Melolonthinae). 3 records from Nomenclature and synonymic remarks on two species of Eupterotidae (Lepidoptera) described by Johan Christian Fabricius, and notes on related species. 6 records from The Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 498 records from Carabidae surveys from the Chronicle of Nature of the Prioksko-Terrasnyi Biosphere Reserve. 17917 records from Insectes Lépidoptères Rhopalocères de France métropolitaine. 187 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 252 records from Données naturalistes de Cyril EPICOCO. 10 records from Dorfrand Mauderode. 21 records from New And Interesting Records Of Plecoptera (Insecta) From Slovakia And Several Autecology Notes. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 68 records from New species and new records of predaceous midges in the genera, Schizonyxhelea Clastrier and Stilobezzia Kieffer from Mexico (Diptera: Ceratopogonidae). 2 records from Studies in Neotropical Pseudophyllinae: A new genus of Cocconotini from the ColombianAndes and new subfamily assignment of the Dominican genus Anacaona (Tettigoniidae: Pseudophyllinae: Cocconotini). 17322 records from K-State Museum of Entomological and Prairie Arthropod Research. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 172 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 4 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 191 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 31 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 50 records from Marine benthic dataset (version 1) commissioned by UKOOA. 14502 records from Propuesta de actualización del Catálogo de Autoridades Taxonómicas (CAT) de Lepidoptera: Heterócera para la Península de Yucatán. 29876 records from European Moth Nights. 50 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 1419 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 22 records from Two new genera of Oriental xyleborine ambrosia beetles (Coleoptera, Curculionidae: Scolytinae). 2897 records from Données d'invertébrés. 2 records from A new addition to the subfamily Anabropsinae (Orthoptera: Anostostomatidae) from China. 104 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 13 records from New species of Tingidae (Insecta: Heteroptera) from Madagascar. 4 records from Four new species and new records of Atopsyche Banks (Trichoptera: Hydrobiosidae) from Pantepui biogeographical region (Venezuela). 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 75 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 25 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 326 records from BUND - Dassower See (Lübeck/Dassow). 58755 records from Données naturalistes de Monsieur François FOURNIER. 36 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 17 records from Schulwald Grundschule Brügge. 6 records from Two new species of the genus Deltomerodes Deuve, 1992 (Coleoptera, Carabidae, Patrobini) from Xizang, China. 5 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 15 records from Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini). 331 records from Administración Nacional de Institutos y Laboratorios de Salud. 8 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 210 records from Cuxhavener Küstenheiden. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 30 records from Revisión del género Microogenius Gutiérrez (Coleoptera: Scarabaeidae: Rutelinae: Rutelini), con descripción de dos nuevas especies altoandinas. 133502 records from Hatikka Observation Database. 267 records from Données naturalistes de Monsieur JOURDE Rémi. 28 records from Wiesenbiotop am Wasserturm. 1 records from A new Atheta species from the West Caucasus and a redescription of A. brevapicalis (Coleoptera: Staphylinidae: Aleocharinae). 115425 records from inatura - Erlebnis Naturschau Dornbirn. 2 records from Report of a new genus Mirigryllus belonging to tribe Modicogryllini, with a new species M. nigrus from Zhejiang, China (Orthoptera: Gryllidae: Gryllinae Modicogryllini). 16253 records from CAS Entomology Type (TYPE). 7 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 97512 records from MfN - Heteroptera Collection. 1834 records from Base de datos de la Colección zoológica del Instituto de Investigación de zonas desérticas de la Universidad Autónoma de San Luis Potosí (BDCZIID-UASLP). 2 records from Myrmica afghanica (Hymenoptera: Formicidae), a new ant species from Afghanistan.. 1 records from A new genus of the Tympanophorus lineage of the subtribe Anisolinina from Madagascar (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 19 records from Mycomystes nigriventris sp. nov. (Coleoptera: Erotylidae: Tritomini) from South America, with insights into the genus Mycomystes Gorham. 2 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 140 records from The Oncometopia orbona species group (Hemiptera, Cicadellidae, Proconiini). 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 4704 records from RNF - Données de l'Association GEREPI (GEstion de la REserve naturelle nationale du PInail). 34 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 5 records from Two new species of the genus Unaspis MacGillivray, 1921 (Hemiptera: Coccomorpha: Diaspididae) from China. 50 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 5 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 173 records from Barcant Butterfly Collection - Papilionidae. 3 records from Description of two new species of ants of the genus Myrmecina Curtis, 1829 (Hymenoptera: Formicidae: Myrmicinae) from the Eastern Himalayas. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 106597 records from Database of invertebrates collected in Mongolia. 4 records from Taxonomic updates for some confusing Micronesian species of Camponotus (Hymenoptera: Formicidae: Formicinae). 3 records from New data of Nazeris Fauvel in Xizang, China (Coleoptera, Staphylinidae, Paederinae). 18 records from Two new species and key to the salina group of the genus Rhagovelia Mayr, 1865 (Hemiptera: Heteroptera: Veliidae) from Colombia. 32853 records from Insect specimen database of Atsugi City Museum. 15 records from New genus and species of Leptopsaltriini (Hemiptera: Cicadidae: Cicadinae) from China and Vietnam, with colour-changing behaviour reported for the first time in Cicadoidea. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 157 records from A Revision of the Nearctic Predaceous Midges in the Bezzia (Bezzia) pulverea complex (Diptera: Ceratopogonidae). 5 records from Three Oriental species of Pseudoaerumnosa Rudzinski (Diptera, Sciaridae) from China. 8 records from Three new species of the Stenus cephalotes group fom Zhejiang, East China (Coleoptera, Staphylinidae). 2978 records from WTSWW Data: All Taxa (West Wales). 8 records from (Table 2) Ostracode distribution in ODP Hole 122-760B. 28 records from ZUEC-GAS - Coleção de Gastropoda do Museu de Zoologia da UNICAMP. 19 records from Census of the fruit and flower chafers (Coleoptera, Scarabaeidae, Cetoniinae) of the Macau SAR, China. 432 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 222 records from Kühmark bei Wetzlar. 14 records from "Ahrschleife bei Altenahr". 101030 records from South Australian Museum Australia provider for OZCAM. 16 records from Regionalpark(Hattersheim). 25 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 517 records from A crowdsourcing approach to collecting photo-based insect and plant observation records. 20 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 68 records from Review of the genus Saropogon Loew, 1847 (Diptera: Asilidae) from Russia Transcaucasia and Central Asia, with description of three new species. 1 records from Description of the last stadium larva of Erythrodiplax abjecta (Anisoptera: Libellulidae) from the eastern Colombian Andes. 811 records from Revision of the Neotropical caddisfly genus Phylloicus (Trichoptera: Calamoceratidae). 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 22 records from Données naturalistes de Cédric POUCHARD. 30 records from Unter hellen Zinnen und finsteren Grotten. 30 records from Données espèces - Expertise IQE 119. 9 records from New data on the genus Syndicus Motschulsky (Coleoptera: Staphylinidae: Scydmaeninae) from Yunnan, southern China. 1 records from Diverse mechanisms of feeding and movement in Cyclorrhaphan larvae (Diptera). 861 records from Inventaire des Rhopalocères. 309 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 10 records from Description of Two New Species of Baeocera Erichson (Coleoptera: Staphylinidae: Scaphidiinae) from México. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 60 records from New State and Host Records for Agromyzidae (Diptera) in the United States, with the Description of Ten New Species. 96535 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 7 records from Two new species of comb-clawed beetles (Coleoptera: Tenebrionidae: Alleculinae) from Yunnan, China. 2 records from An enigmatic new genus of cyclostome braconid wasp (Hymenoptera: Braconidae) from New Zealand. 138 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 4 records from Données naturalistes de Noé Conservation. 11 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 13 records from Golf de Chantilly. 48 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 2 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 1 records from A complementary description of the male of Kyphopteryx yangi (Plecoptera: Taeniopterygidae) from China. 3 records from Faunal assemblage of sediment core TR149-32. 266 records from Revision of the genus Doryscus Jacoby (Coleoptera: Chrysomelidae: Galerucinae). 118 records from Naturalis Biodiversity Center (NL) - Pisces. 1222 records from Ichneumonidae (Hymenoptera) de la reserva de la biosfera El Cielo, Tamaulipas. 3711 records from Dipterists Forum: Field Week 2015 (Nottinghamshire). 25 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 46 records from Données naturalistes d'Emmanuel SECHET. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 12365 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 1798 records from Seasearch Marine Surveys in England. 17 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 21 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 8 records from A revision of the genus Rhinotorus Förster, 1869 (Hymenoptera, Ichneumonidae, Ctenopelmatinae), with descriptions of three new species and an illustrated identification key. 15 records from Discontinuous color variation in the assassin bug species Tiarodes miyamotoi (Hemiptera: Reduviidae: Reduviinae). 13 records from The discovery of Lepidocyrtoides Schött, 1917 (Collembola, Entomobryidae, Entomobryinae) from the New World, including three new species from Brazil and one from Australia. 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 1295 records from Riqueza de especies y biodiversidad edáfica de una zona de humedales del Parque Nacional Arrecife de Puerto Morelos, Quintana Roo, México. 14009 records from Collection Trichoptera - SMF. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 39 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 1 records from Three new species of the family Scathophagidae (Diptera) from the Palaearctic region with a redescription of the male of Amaurosoma longicorne. 4 records from A new species of Sarcofahrtiopsis (Insecta, Diptera, Sarcophagidae) from mangrove forests in the Brazilian Amazon, with a key to species identification. 42 records from Studies of Ptiliidae (Coleoptera) in the Spirit Collection of the Natural History Museum, London, 6: New species and records collected by W. C. Block in Kenya and Uganda, 1964 - 1965. 640 records from Soil Invertebrates Surveys from the Chronicle of Nature of the Prioksko-Terrasnyi Biosphere Reserve. 126 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 1 records from Description of a new species of Neocordulia Selys, 1882 (Odonata: Libellulidae, Corduliinae) from southern Brazil. 137587 records from Arizona State University Hasbrouck Insect Collection. 2 records from From an old sound recording to a new species in the genus Horatosphaga (Orthoptera: Tettigonioidea: Phaneropterinae: Acrometopini). 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 39 records from Integrating data to redescribe Euschistus taurulus Berg (Hemiptera: Pentatomidae). 187 records from Enquête Laineuse du Prunellier (OPIE). 1167 records from Woodmeadow Invertebrate Survey 2018. 8 records from A new species of the genus Chrysacris Zheng, 1983 from China (Orthoptera: Acridoidea, Acrididae). 429 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 154 records from A Taxonomic Revision of Nearctic Conostigmus (Hymenoptera: Ceraphronoidea: Megaspilidae). 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 57 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 25 records from Taxonomic revision of the genus Hirotophora Brown et al. (Diptera: Phoridae) with the description of a new species from Chile. 1 records from A new species and a new record of genus Hexacentrus Serville, 1831 (Orthoptera: Tettigoniidae: Hexacentrinae) from India. 11 records from BID-AF2015-0004-NAC Collection de Diptères du LEA-UL. 156 records from Chironomid remains in the sediment sequence of Site PG1212. 7 records from Two new remarkable genera and two new species of Gyponini (Hemiptera: Cicadellidae: Iassinae) from Brazil. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 125 records from Inventaire participatif des rhopalocères de Bois-Guillaume, Bihorel et Isneauville. 2 records from A new genus, Perplexacara, and new generic placements of species of Australian marsh beetles (Coleoptera: Scirtidae) based on morphology and molecular genetic data. 69400 records from MDFRC macroinvertebrate survey. 1 records from Rhysacephala masneri n. sp. (Xiphydriidae), the first symphytan wasp recorded from Lord Howe Island. 1 records from HBRG Fungus, Lichen & Lower Plants Dataset. 15 records from Amtsrain Apolda-Zottelstedt. 6 records from Morphology of the males of seven species of Ortheziidae (Hemiptera: Coccoidea). 31 records from New species and records of Cladiopsocus Roesler (Psocodea: ‘ Psocoptera’: Psocomorpha: Cladiopsocidae) from Colombia. 12 records from A new species of genus Trilocha Moore, [1860] from Great Nicobar Island, India (Lepidoptera, Bombycoidea, Bombycidae). 120 records from Bothynus entellus (LePeletier & Serville) (Coleoptera: Scarabaeidae: Dynastinae) species group: taxonomic revision and description of two new species. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 39 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 4 records from Onthophagus fragosus n. sp. a second endemic species of Onthophagus Latreille from Cuba (Coleoptera: Scarabaeidae, Scarabaeinae). 1833 records from Données du naturaliste DELAPRE Jean-Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 1 records from The genus Alphocoris in the Indomalaya (Hemiptera: Heteroptera: Scutelleridae). 140 records from Swedish Malaise Trap Project (SMTP) - Braconidae: Cheloninae: Adelius. 5 records from New species of the non-biting midges of Tribe Chironomini (Dptera, Chironomidae) from the Bolshekhekhtsyrsky Reserve (Russia, Khabarovsk Territory). 4 records from Two new species of Podonomus Philippi (Diptera: Chironomidae: Podonominae) from mountains of Southeastern Brazil. 31 records from New Descriptions Of North American Taenionema Larvae (Plecoptera: Taeniopterygidae). 281 records from Ecología e historia natural de Schistocerca americana socorro y S. piceifrons piceifrons en Isla Socorro. 11 records from Schulgelände Lise Meitner Realschule (Paderborn). 106 records from Coloration variability of the Oriental genus Agnorimus Miyake & Iwase, 1991 (Coleoptera: Scarabaeidae, Cetoniinae) with synonymic notes. 38 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 66 records from First catalogue of the Asopinae (Hemiptera, Pentatomidae) from French Guiana. 62 records from Revision of the Madagascan genera Oncodopus Brongniart and Colossopus Saussure (Orthoptera: Tettigoniidae: Conocephalinae; Euconchophorini), with description of Malagasopus gen. nov.. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 11 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 1759 records from Meetnetten.be - Site counts for butterflies in Flanders, Belgium. 39 records from Swedish Malaise Trap Project (SMTP) - Formicidae. 52 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 2 records from A new species of the assassin bug genus Rihirbus (Hemiptera: Heteroptera Reduviidae) from Vietnam. 40 records from Review of the Catocala delilah species complex (Lepidoptera, Erebidae). 2 records from Species of the genus Chrysotus Meigen, 1824 (Diptera: Dolichopodidae) from Japan, with descriptions of two new species. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 129891 records from Suivi Temporel des Rhopalocères de France (STERF). 43 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 1 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during HEINCKE cruise HE133. 157686 records from All taxa records for Leicestershire and Rutland. 6 records from Données naturalistes de NOËL Rémi. 1 records from Pollen analysis of sediment profile KR0 from Kreutzsee. 334 records from GEN_TEREO_2017_12_18. 6 records from First description of the male caste of the Himalayan endemic ant Lasius alienoflavus Bingham, 1903 (Hymenoptera: Formicidae), with re-description of the female and queen castes. 77 records from Fossil specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 307 records from Type Localities of Heteroptera (Insecta: Hemiptera) from Turkey. 17 records from Two new species of Balacha (Insecta: Hemiptera: Cicadellidae: Cicadellinae) from Brazil with comments on their phylogenetic position and biogeography. 1 records from La Côte oubliée - La Planète Revisitée - Nouvelle-Calédonie 2017. 6 records from Landwehrbach. 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 9 records from A new genus and species of Oxycarenidae (Hemiptera, Heteroptera, Lygaeoidea) from Argentina. 1700 records from Inventaire entomologique standardisé des ZNIEFF de Martinique, protocole utilisé en 2014 et 2015. 9 records from A new species of Pothea, with new records and taxonomic notes on other species of the genus (Hemiptera: Heteroptera: Reduviidae). 42 records from A new species of the grass-feeding leafhopper genus Amblysellus Sleesman (Hemiptera: Cicadellidae: Deltocephalinae) from western Mexico, with a checklist and key to species. 401 records from Données de VINCENT Alexis (SAPROX). 8 records from Regenrückhaltebecken Bad Bevensen. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 55 records from Three new species of Ametadoria Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, Costa Rica. 20 records from Catalogue of the primary types of marine molluscan taxa described by Tommaso Allery Di Maria, Marquis of Monterosato, deposited in the Museo Civico di Zoologia, Roma. 6 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 1171 records from Glasgow Museums BRC: Chrysomelidae. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 2 records from A new species of Symbiopsocus Li (Psocodea: “ Psocoptera ”: Psocidae) from Taiwan, China, with a revised checklist and key to species. 27 records from New Species And Records Of Anacroneuria (Plecoptera: Perlidae) From Ecuador And Paraguay. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 43 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 999882 records from Texas A&M University Insect Collection. 20 records from A new genus Viperinus Park with descriptions of two new species, and two new species of the genus Protolychnis Meyrick, 1925 (Lepidoptera, Gelechioidea, Lecithoceridae) in Kenya and Tanzania, with a checklist of the world species. 214 records from Insectarium René-Martineau (IRM). 4 records from New information on the skipper fauna of Guangxi, China (Lepidoptera, Hesperiidae). 1336 records from Inventaire éclair de Natureparif - Année 2015. 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 50 records from Palynological investigation of profile Tso Kar. 82 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 718 records from Cepora butterfly specimens at Museum Zoologi Bogor, Indonesia. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 8005 records from Tour_du_Valat_2017_12_18. 6 records from The uncommon Neotropical genus Pazius Navás, 1913 (Mecoptera: Bittacidae): a comprehensive synthesis, with description of a new Brazilian species. 3 records from A new mayfly species of Rhoenanthus (Ephemeroptera: Potamanthidae) from Peninsular India. 5 records from A new genus and species of Neotropical Nemobiinae (Insecta: Orthoptera: Grylloidea: Trigonidiidae: Nemobiinae). 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 20 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 1 records from Fossil Specimens of Komatsu City Museum. 37 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 9 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 8 records from New species of Donda Moore, 1882 and new data on Pantheinae species. Revision of Pantheinae, contribution XIV (Lepidoptera, Noctuidae: Pantheinae). 2318 records from Données naturalistes de Bernard Lalanne-Cassou. 8 records from First report of the genus Phytodietus Gravenhorst, 1829 (Hymenoptera: Ichneumonidae: Tryphoninae) from Thailand. 5 records from A new monotypic genus, a species synonymy and nomenclatural corrections in the arid-adapted Canthonini (Scarabaeidae, Scarabaeinae) from the Succulent Karoo Biome of south-western Africa. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 779 records from Données naturalistes de Xavier CUCHERAT. 1402 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 2 records from A new species of the genus Hesperempis Melander (Diptera: Empididae) from Siberia. 4 records from The Chinese species of the genus Phlaeopterus Motschulsky, 1853 (Coleoptera Staphylinidae: Omaliinae: Anthophagini). 59 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 390 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 1642 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 7 records from Four new species of Scydmaeninae and Pselaphinae (Coleoptera: Staphylinidae) from Yunnan, China. 17 records from A molecular phylogeny of Speonemadus Jeannel, 1922 with description of two new species from Morocco (Coleoptera: Leiodidae: Cholevinae: Anemadini). 4 records from First report of the genus Tettigonia Linnaeus (Orthoptera: Tettigoniidae: Tettigoniinae) and record of Tettigonia caudata caudata (Charpentier, 1842) from India. 8 records from Gergithoides Schumacher, 1915 in Vietnam, with two new species, and taxonomic notes on the genus (Hemiptera: Fulgoromorpha: Issidae). 94 records from The Dragon-flies (Odonata) of Palestine, based primarily on collection made by Dr. P. A. Buxton, with Notes on the Species of the Adjacent Regions.. 63 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 7590 records from Lepidoptera of Mordovia State Nature Reserve. 8 records from Colección Invertebrados-Museo de Historia Natural Unillanos. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 58 records from The mutillid wasps of the Dasymutilla paradoxa species-group (Hymenoptera, Mutillidae). 6 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 17 records from Neue Arten der Gattung Atomaria STEPHENS, 1830 aus der Türkei und dem Irak (Coleoptera, Cryptophagidae). 12 records from New species of the Neotropical genus Campatonema Jones (Geometridae, Ennominae) with the first description of the female. 16 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 1098 records from What bug is that. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 7407 records from Dipterists Forum: Field Week 2018 (Stoke). 2 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 4 records from Two new species of Kamimuria (Plecoptera: Perlidae) from Shaanxi Province, China. 3 records from A new species of the genus Neobubastes Blackburn, 1892 from Western Australia (Coleoptera: Buprestidae: Buprestinae: Pterobothrini). 9 records from Five new species of the genus Noeetomima Enderlein (Diptera: Lauxaniidae) from China, with a key to world species. 5 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 4 records from Warnowufer Groß Klein. 20 records from Heteroptera - SMNG. 3 records from Paleotelmatoscopus, a proposed new genus for some fossil moth flies (Diptera Psychodidae, Psychodinae) in Eocene Baltic amber, with description of a new species. 149 records from Données du/de la naturaliste DEHONDT François provenant de la base de donnée du SINP Île-de-France CETTIA. 9827 records from Meetnetten.be - Population counts for dragonflies in Flanders, Belgium. 221 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae Anthophagini) of the Iberian Peninsula. 56 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 78 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 1924 records from Modernisation des ZNIEFF du PnrL. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 22 records from Collection Mantodea - SMF. 102 records from Swedish Malaise Trap Project (SMTP) - Evaniidae. 46 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 179 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 20 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 356 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 87262 records from Taiwan Forestry Research Institute. 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 33695 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 31229 records from DIPOL. 92 records from A list of coleoptera recorded in Mixed Forest habitat in Arabuko-Sokoke Forest, Kenya. 478 records from MfN - Fossil invertebrates IIb. 1562 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 107039 records from Tasmanian Museum and Art Gallery provider for OZCAM. 820 records from Données de la structure Fédération 77 de Pêche et Protection du Milieu aquatique provenant de la base de donnée du SINP Île-de-France CETTIA. 83 records from UAM Invertebrate Collection (Arctos). 13 records from Diglotta mersa (Haliday) and Halobrecta flavipes Thomson, two new species for the Canadian fauna (Coleoptera, Staphylinidae, Aleocharinae). 4 records from Discovery of the first pincer wasp (Hymenoptera, Dryinidae) from Rovno amber. 11 records from A new genus of Pexicopiini (Lepidoptera: Gelechiidae) for “ Gelechia ” acanthopis Meyrick, 1932, with review of functional morphology of male genitalia in allied genera. 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 41 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 620 records from World revision of Iteaphila with unbranched radial vein (Diptera: Empidoidea: Iteaphilidae). 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 73 records from Données du/de la naturaliste Livet Bertrand provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from Sexual variation in two species of Helorus Latreille (Hymenoptera, Heloridae) from NW China, with description of female of Helorus caii He & Xu. 133 records from SNH Invertebrate Site Condition Monitoring 2013/14: Black Wood of Rannoch SSSI. 1287 records from Revision of Anisepyris Kieffer (Hymenoptera, Bethylidae), with description of 135 new species. 6 records from Three new species of Willowsia (Collembola: Entomobryidae) from Guizhou Province, China. 95 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2312 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 22 records from Megymenum tuberculatum, a new species of Megymenini from Java and a review of distribution of M. brevicorne (Hemiptera: Heteroptera: Dinidoridae). 14 records from Tejidos de los ejemplares colectados en la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 175 records from Revisión taxonómica de Pseudococcus Westwood (Hemiptera: Pseudococcidae) de Centro y Sud América con descripciones de especies nuevas. 768 records from Mollusca collection of National Museum of Nature and Science. 1 records from A dryinid wasp in Early Eocene amber from the Paris basin (Hymenoptera: Dryinidae). 124 records from Zur Taxonomie und Verbreitung einiger westpaläarktischer Arten der Gattung Planeustomus J V (Coleoptera, Staphylinidae, Oxytelinae). 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 32144 records from Alterra (NL) - Entomofauna inventory in peat swamps. 197 records from The Genus Megaleuctra Neave (Plecoptera: Leuctridae) In North America. 110 records from Integrative revision of the Iberian species of Coscinia Hübner, [1819] sensu lato and Spiris Hübner, [1819], (Lepidoptera: Erebidae, Arctiinae). 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 6 records from Taxonomic revision of the genus Glenopopillia (Coleoptera: Scarabaeidae: Rutelinae). 54 records from Jumping plant-lice (Hemiptera: Psylloidea) of Afghanistan. 3 records from Données du naturaliste Jérôme Hanol. 140 records from Bayerische Donau - Leipheim. 582686 records from NMNH Extant Specimen Records. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 76 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 1 records from Extracellular DNA marine sediment Targeted Locus (Loci). 1 records from Neoperla Of Unusual Size From Vietnam (Plecoptera: Perlidae). 2 records from Description of a new species of the genus Paraedes (Diptera: Culicidae) in Assam, India. 1 records from Notes on and key to the genus Phengaris (s. str.) (Lepidoptera, Lycaenidae) from mainland China with description of a new species. 1 records from Upsa centennial, a new genus and species (Coleoptera: Scarabaeidae: Scarabaeinae: Endroedyolini) from the Southern Mistbelt forest in South Africa celebrating 100 years of entomology at the University of Pretoria. 3 records from A new species of Hemilea Loew and two new records of Trypetini (Diptera Tephritidae: Trypetinae) from India. 10 records from "Schwarzwassertal" bei Pobershau. 15 records from Taxonomic revision of a darkling beetles genus Anaxius (Tenebrionidae: Pedinini: Helopinina). 58 records from Données de la structure OGE (Office de Génie Ecologique) provenant de la base de donnée du SINP Île-de-France CETTIA. 53 records from The vespid fauna of Pakistan. 1 records from A new reticulated beetle (Coleoptera: Cupedidae) from Mexico with a catalogue of Cupedidae species of the world. 3 records from Plan de vertebrados de la Patagonia. 1170 records from Springtales from lichen communities at Kollåsen in Norway. 10 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 1466 records from Données du naturaliste ROUDIE Gilbert provenant de la base de donnée du SINP Île-de-France CETTIA. 18 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 15 records from Two new genera and two new species of cicadas from Central America (Hemiptera: Cicadidae: Cicadinae). 6187 records from Données naturalistes de Nathalie POT. 34048 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 4 records from Macrofauna abundance in surface sediment sampled during cruise DI226. 34 records from Five new species and a new record of Sathytes Westwood from eastern China (Coleoptera: Staphylinidae: Pselaphinae). 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 426 records from Danielsberg (Mölltal, Kärnten). 12410 records from Biodiversity4all Research-Grade Observations. 66 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 7897 records from LPO_PACA_2017_12_18. 141 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 1 records from A new species of the Australian genus Clinopsocus New from coastal California (Psocodea: ‘ Psocoptera’: Elipsocidae). 4 records from When Citizen Science highlights alien invasive species in France: the case of Indochina mantis, Hierodula patellifera (Insecta, Mantodea, Mantidae). 630 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 1 records from Liste des pays par taxon spécimen TOGO. 192 records from DNA barcoding and morphology reveal a new cryptic species of Nagiella (Lepidoptera, Crambidae, Spilomelinae) from Japan. 774 records from Studies in Hawaiian Diptera III: New Distributional Records for Canacidae and a New Endemic Species of Procanace. 313 records from Abundance of macroinvertebrates in sites with varying degradation levels in Lake Wamala. 1 records from Macrofauna biomass in surface sediment sampled during cruise DI229. 8 records from New Hemilophini, Aerenicini and Calliini from French Guiana, transference and notes on Hemilophini (Coleoptera, Cerambycidae, Lamiinae). 401 records from The empidoid flies (Diptera: Empidoidea, exclusive of Dolichopodidae) of the Russian Arctic islands and Svalbard Archipelago. 2 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 8 records from A new species of Ferorhinella (Hemiptera: Cercopidae) from southeastern Brazil with taxonomic notes on the genus. 98 records from The genus Pholetesor Mason, 1981 (Hymenoptera, Braconidae, Microgastrinae) from China, with descriptions of eleven new species. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 23 records from New Black Fungus Gnats (Diptera, Sciaridae) of North America. Part II. Genus Bradysiopsis Tuomikoski, 1960. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 36 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 10 records from Artensuche auf den Elbwiesen in Radebeul. 200 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 36 records from The genus Lyroda Say, 1837 in Africa and Arabian Peninsula with description of two new species (Hymenoptera, Crabronidae). 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 4771 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 18 records from JOHN W. BROWN (2019) New genera, new species, and new combinations in new world Cochylina (Lepidoptera: Tortricidae: Tortricinae). Zootaxa, 4671 195 - 222.. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 7 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 13 records from A new species of Soikiella Nowicki (Hymenoptera: Trichogrammatidae) from Italy. 4 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 11 records from Tümpel Schulbiologiezentrum. 37 records from Naturschutzgebiet Lüneburger Heide. 2 records from ESA herbarium - Universidade de São Paulo - Herbário Virtual REFLORA. 3 records from The Genus Pseudopomyza (Diptera: Nerioidea) in Tasmania, with Description of a New Species. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 1284 records from Collection of Heteroptera. 25 records from Landschaftspflegehof (Berlin). 140 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 5 records from Bachpatenschaft Beeke. 4 records from One new species of the genus Xizicus Gorochov, 1993 (Orthoptera: Tettigoniidae Meconematinae) from Guangxi, China. 461 records from Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 50 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 122 records from Checklist of Cerambycidae (Coleoptera) primary types of the Coleção Entomológica Pe. Jesus Santiago Moure, Departamento de Zoologia, Universidade Federal do Paraná, Curitiba, Paraná, Brazil, Instituto Nacional de Pesquisas da Amazônia, Amazonas, Manaus, Brazil, and of the Museu Paraense. 176 records from A checklist of the Robber Flies (Insecta: Diptera: Asilidae) of Wyoming, USA. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 1228 records from Jena Microbial Resource Collection (JMRC) at Leibniz Institute for Natural Product Research and Infection Biology e.V. Hans-Knöll-Institute (HKI) and Friedrich Schiller University Jena. 43 records from Artenvielfalt auf den Elbwiesen (Dessau). 4647 records from Swedish Malaise Trap Project (SMTP) - Dolichopodidae. 40 records from Données naturalistes de Daniel PAVON. 26 records from Two new tiger beetle species (Coleoptera: Cicindelidae) from Myanmar and notes on another species. 151. Contribution towards the knowledge of the Cicindelidae. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 29 records from Actualización de la base de datos de colémbolos de México. 5 records from Discovery of a new species of Trieces (Hymenoptera: Ichneumonidae: Metopiinae) questioning the traditional delimitation between Trieces and Chorinaeus. 336 records from Malawi-Saturniidae-Biodiversity-Data. 8 records from Order Diptera, family Mydidae. 1 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 44534 records from Estonian Nature Observations Database. 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 71 records from Seasearch Marine Surveys in the Channel Islands. 2 records from Global phylogeography survey of thermophilic spores in marine sediments.. 34 records from Etude d'impact de la ZAC Bellevue - compléments. 2 records from A new species of Seira (Collembola: Entomobryidae) from northeastern Brazil. 4 records from Two new species of the genus Scaphidium Olivier (Coleoptera: Staphylinidae Scaphidiinae) from Southwest China. 122 records from A second update to the checklist of Finnish long-legged flies (Diptera: Dolichopodidae), with a re-evaluation of the status of Hydrophorus callosoma Frey, 1915. 355 records from Données naturalistes de Jean-Michel LEMAIRE. 7 records from Two new species of Batrisodes Reitter from Shaanxi, China (Coleoptera Staphylinidae: Pselaphinae). 11851 records from Fife Nature Records Centre combined dataset. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 5 records from A new species of Contarinia (Diptera: Cecidomyiidae) damaging inflorescence of Carya cathayensis (Juglandaceae) in China. 59 records from Revision of Pyrrhalta (Coleoptera: Chrysomelidae: Galerucinae) species with maculate elytra. 18 records from A revision of Pinobius. II. Three new species from Cambodia and Indonesia, and additional records (Coleoptera: Staphylinidae: Paederinae). 9 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 1 records from The genus AnTonia Loew in Egypt: A. gabalensis El-Hawagry, a new synonym of A. feDTschenkoi Loew (Antoniinae, Bombyliidae, Diptera). 14 records from Naturschutzgebiet Lochbusch-Königswiesen. 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 70 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 25 records from Review of the genus Macropsis Lewis, 1836 (Homoptera: Auchenorrhyncha Cicadellidae: Eurymelinae: Macropsini) of Southeastern Kazakhstan with description of new species. 124 records from Données du naturaliste Calvel Dominique provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage. 1970 records from Dipterists Forum: Field Week 1981 (Kent). 11 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 1 records from Eulachon migration bottom trawl surveys. 3477 records from Arthropod fauna in christmas tree plantations. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 2 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 13 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 85 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 17 records from Heavy minerals of sediment core PL94-64. 116 records from Deanophlebia: A new genus of south-eastern Australian mayflies and subsequent redefinition of the subgenus Nousia (Australonousia) (Ephemeroptera: Leptophlebiidae). 2100 records from Dolichopodidae of Portugal - dataset 2009-2018. 4 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 1578 records from Données naturalistes de Christophe HANOT. 72 records from Données du naturaliste Mael Garrin. 9 records from Notes on Oriental Clivinini and the description of two new species (Coleoptera: Carabidae: Clivinini). 1 records from Cheiloneurus flaccus (Walker, 1847) (Hymenoptera: Encyrtidae), new to New Zealand. 15 records from Two new species of the genus Sinotilla Lelej, 1995 (Hymenoptera: Mutillidae), with notes on taxonomic characters. 15 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE255. 59 records from Crickets of the subfamily Itarinae Shiraki, 1930 (Orthoptera: Gryllidae) from China with description of a new species and distribution and critical notes on other species. 1 records from Revision of the Recent Alvania scabra (Philippi, 1844) complex (Mollusca, Gastropoda Rissoidae) from the Mediterranean Sea with the description of a new species. 7 records from Two new species of Eumeninae from Iran (Hymenoptera: Vespidae). 2922 records from Données naturalistes d'Alain BERLY. 37 records from COA Entomology Collection (Arctos). 39130 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 26 records from Feriendorf des Kreises Gedern (Ober-Seemen). 530 records from Données opportunistes. 2 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 122 records from Caracterização do grupo Edessa rufomarginata e descrição de sete novas espécies (Heteroptera, Pentatomidae, Edessinae). 6 records from A new fossil species of Trentepohlia (Diptera, Limoniidae) from the Dominican Miocene. 11 records from New species of Australopericoma Vaillant (Diptera: Psychodidae) from the Brazilian semiarid region and key to males of the genus. 1 records from Leeuwenia hollisi sp. n. (Thysanoptera, Phlaeothripinae) from New Guinea, with the tenth abdominal segment exceptionally long. 54 records from Inventaire et regroupement de données Natura 2000. 1 records from First report of the genus Longipalpus Montrouzier, 1861 (Coleoptera: Cerambycidae: Cerambycinae) from India with the description of a new species. 17 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 5 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 18 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 51 records from The Plecoptera of Panama. III. The genus Anacroneuria (Plecoptera: Perlidae) in Panama’s national parks: 2017 survey results. 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 1426 records from Korean Insect Database. 516 records from Étude biodiversité toitures végétalisées d'Île-de-France réalisée par Natureparif / ARB. 40 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 2 records from Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 885 records from Species biodiversity transnational geo-database - IMPRECO Project. 309 records from A revision of the water beetle genus Hydraena Kugelann for southern Africa (Coleoptera: Hydraenidae). 4 records from Description of three new species of Encyrtidae Walker (Hymenoptera: Chalcidoidea) from India. 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 2284 records from Données du naturaliste Maillard Bernard provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new species of Pelecium Kirby (Coleoptera: Carabidae: Peleciini) from the Atlantic Forest biome, Brazil. 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 1 records from A new species of the genus Mongolotettix Rehn, 1928 from Hubei, China (Acrididae, Acridoidea, Orthoptera). 289 records from bmhs_butterfly_collection. 7 records from BIRDRACE Birding Bentheim. 1 records from Tagalis graziae, a new species of Saicinae from the Chocó biogeographic region in Colombia (Hemiptera: Reduviidae). 218 records from The jumping plant-lice (Hemiptera: Psylloidea) of Belarus. 110866 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 4 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 1115 records from Données opportunistes sur les rhopalocères. 1 records from SWECO. 1336 records from Données naturalistes de Loïc SALAUN. 261 records from Taxonomic review of Tipula (Vestiplex Bezzi) crane flies (Diptera: Tipulidae) in Mongolia. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 2 records from Taxonomic review of Stictophaula (Orthoptera: Phaneropterinae) with the description of one new species from Brunei Darussalam. 1 records from Discovery of termitophilous tenebrionid beetles in China (Coleoptera: Tenebrionidae). 577 records from East Ayrshire Species Database. 100 records from Euroants. 10526 records from Données du naturaliste DEHALLEUX Axel provenant de la base de donnée du SINP Île-de-France CETTIA. 12 records from A new species of Nerice Walker, 1855 and further additions to the catalogue of Indian Notodontidae Stephens, 1829 (Lepidoptera: Noctuoidea) from Himalaya with report of range extensions. 1976 records from Insect Collection of the Laboratory of Applied Entomology of the Faculty of Sciences of the University of Lome. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1564 records from Leif Richardson Vermont Bee Specimens. 247 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 111 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 147 (N.S) n° 40 (3), 2012 - Données faune. 2 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 7 records from Collection Crustacea - ZMB. 9 records from Macrocydia divergens, a new genus and species of Grapholitini (Lepidoptera: Tortricidae: Olethreutinae) from Central America. 1 records from A new species of Chiridurothrips Okajima from Miocene amber of the Dominican Republic (Thysanoptera: Phlaeothripidae). 9 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 4 records from Taxonomic study of the genus Meganola (Lepidoptera, Nolidae, Nolinae), with three new species and a new record from China. 6 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 16 records from Five new species of the genus Dindymus (Heteroptera: Pyrrhocoridae). 50 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 23 records from A Middle Devonian Trilobite Assemblage from Venezuela. 47 records from Three new species and six new records of Scathophagidae (Diptera) from Japan with a key to the Japanese genera. 5 records from Settlement of the classification of Svistella Gorochov and Paratrigonidium Brunner von Wattenwyl using morphology and molecular techniques, with the description of a new species from Yunnan, China (Orthoptera: Trigonidiidae: Trigonidiinae). 9 records from Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA. 110 records from Insectos del páramo de Sumapaz, Cundinamarca - Proyecto Colombia Bio. 11 records from New species of Rivudiva Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae) with comments on R. minantenna Lugo-Ortiz & McCafferty and R. trichobasis Lugo-Ortiz & McCafferty. 154 records from Dermaptera in the icipe collection. 49 records from Données naturalistes de Maxime BEAUJEON. 33 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 10 records from A new species of Bomansius Lacroix (Coleoptera: Lucanidae) from Vanuatu, with redescriptions of its genus and its only congener, Bomansius gabrieli Lacroix, 1978. 65 records from Three new species and new records of cuckoo bees of the genus Epeolus in Turkey (Hymenoptera: Apidae: Nomadinae). 11 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 69 records from The national database for marine data (MADS). 467 records from Noctuidae brasileiros de importancia economica depositados na coleção MNHUK. 975 records from Röntgenarchiv Wilhelm Stürmer - SMF. 51 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 23 records from New synonyms of Euconnus (Tetramelus) kraussi Reitter, 1880 (Coleoptera Staphylinidae, Scydmaeninae). 8 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 6 records from Invasive Alien Species in Denmark. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 25 records from Données du/de la naturaliste RAMBAUD Maxime provenant de la base de donnée du SINP Île-de-France CETTIA. 12 records from Three new species of Seira Lubbock (Collembola, Entomobryidae, Seirinae) from Madagascar with Lepidocyrtus - like habitus. 7814 records from Odonata de Veracruz. 1 records from BIRDRACE Niederlausitz-Team. 171 records from Revisions to the faunas of Andrena of the Iberian Peninsula and Morocco with the descriptions of four new species (Hymenoptera: Andrenidae). 712 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 3 records from New European records of Ditomyia macroptera Winnertz (Diptera: Ditomyiidae) with notes on its distribution. 4 records from Four new species of tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) from the Afrotropical Region. 478 records from Revision of some types of North American aleocharines (Coleoptera: Staphylinidae: Aleocharinae), with synonymic notes. 1 records from A new mesoserphid wasp from the Middle Jurassic of northeastern China (Hymenoptera, Proctotrupoidea). 42 records from Two new species of Tipula (Vestiplex) Bezzi (Diptera, Tipulidae) from Northwest China. 62 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 11 records from Notes on Onciderini (Coleoptera, Cerambycidae, Lamiinae): description of a new species of Lesbates Dillon & Dillon and new distribution records. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 38 records from A new species of Elachiptera Macquart from the Galápagos Islands, Ecuador, and the taxonomic status of Ceratobarys Coquillett (Diptera: Chloropidae). 15 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 22 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 2 records from Collection Herpetology SMF. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 4 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 1 records from A new species of Tyrannomyrmex (Hymenoptera: Formicidae: Myrmicinae) from India.. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 92 records from Archives of the Arctic Seas Zooplankton. 56 records from CG04_2017_12_18. 10 records from Two new taxa of Plebejus Kluk, 1780 (Lepidoptera, Lycaenidae) from the Gobi desert, Mongolia. 10 records from The Winter Stoneflies (Plecoptera: Capniidae) Of Mississippi. 88 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 16 records from The Fish Collection. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 126 records from Collection Ephemeroptera - SMF. 514 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 651 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 55 records from Additions and corrections to the systematics of mayfly species assigned to the genus Callibaetis Eaton 1881 (Ephemeroptera: Baetidae) from South America. 102437 records from Denver Museum of Nature & Science - Entomology. 12 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 3 records from Pelagic Microbiome: viruses to protists. 16S and 18S data from oceanic samples collected at the chlorophyll maximum.. 2 records from Entyposis cordipenis new species from Ethiopia (Coleoptera: Scarabaeidae: Melolonthinae: Schizonychini). 6 records from Hedotettix angulatus sp. nov. (Orthoptera: Tetrigoidea: Tetrigidae, Tetriginae) a new pygmy grasshopper species from India. 221 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 5522 records from Butterflies (Lepidoptera: Lycaenidae) Occurrence Data in Sub-Saharan Africa. 101 records from RISC Non-Native Species Records for Rhododendron Leafhopper. 34 records from Naturschutzstation Schmidsfelden. 6 records from Spider (NSMK-SP). 3 records from BB-Biodiversität b. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 282 records from National Biodiversity Data Bank. Observation records, 1900-2014. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 13 records from Contribution to the knowledge of the Prioninae (Coleoptera, Cerambycidae) from the Mizoram State (India), with the first report of the genus Megobaralipton Lepesme & Breuning and new records from the country. 27 records from The genus Anaphothrips (Thysanoptera, Thripidae) in China, with three new species. 2 records from VFD-H: Heidenrod: Pferdeweide Mürth. 29477 records from Manitoba Museum of Man and Nature. 12402 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 12688 records from Caddisfly (Trichoptera) records from Britain and Ireland, via iRecord. 2 records from Two new species of Corynellus Bates, 1885 (Coleoptera: Cerambycidae: Cerambycinae). 23 records from Taxonomic review of Coccobius species (Hymenoptera: Aphelinidae) from China, with notes on their use in biological control of scale insect pests (Hemiptera: Diaspididae), and description of a new species. 6 records from Two new terrestrial species of Hydraena Kugelann from the island of Bioko, Gulf of Guinea (Coleoptera: Hydraenidae). 182 records from Revision of the ant genus Mayriella.. 6 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 17 records from Nottekanal, Klasse 7 - 10. 77 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 831 records from RNF - Données du Parc Naturel Régional de la Forêt d'Orient. 1 records from The fossil crown wasp Electrostephanus petiolatus Brues in Baltic Amber (Hymenoptera, Stephanidae): designation of a neotype, revised classification, and a key to amber Stephanidae. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 45 records from Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 477 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 4 records from Données espèces - Expertise IPE 69. 8 records from Données taxonomiques et éthologiques nouvelles sur quatre espèces de Cigales du Sud thaïlandais (Rhynchota, Cicadoidea, Cicadidae). 3 records from A new species of the genus Sovia Evans, 1949 from South Central Yunnan, China (Lepidoptera, Hesperiidae). 159 records from A review of the gall midges (Diptera: Cecidomyiidae) of Indonesia: taxonomy, biology and adult key to genera. 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 5 records from ------ A- ----- new- ----- species- ----- of- ----- the- ----- genus ------ Toleria- ----- Walker, ------ [1865] ------ from- ----- northern ------ Vietnam- ----- and Laos- ----- with- ----- establishment- ----- of- ----- a- ----- new- ----- generic ------ synonymy- ----- in- ----- Cissuvorini- ----- (Lepidoptera Sesiidae). 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 2 records from Description of Coeliccia bhriulieci sp. nov. (Odonata: Zygoptera: Platycnemididae) from central Vietnam. 12 records from Révision du genre Paradorodocia Machatschke, 1957 (Insecta, Coleoptera, Rutelidae, Adoretinae). 26 records from Pachyprotasis kojimai sp. nov. — the “ Pachyprotasis nigronotata ” of Japanese authors (Hymenoptera: Tenthredinidae). 3 records from Two new species of Sphaeronemoura (Plecoptera: Nemouridae) from Oriental China. 174 records from Chronicle of Nature - Phenology of Insects of State Nature Reserve Malaya Sosva. 3 records from Sammlung Clemens Borneo Herbarium Hamburgense HBG. 1 records from Flora und Fauna im Brexbachtal. 652 records from Insectos asociados a cultivos de Albahaca y Ají en Santa Marta. 82 records from Inventaire Faune. 6 records from MICROBIS database. 9 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 1144 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 36 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 485667 records from Swiss National Grasshoppers Databank. 27 records from New Mixaderus species from the Mascarene Islands (Coleoptera: Aderidae). 3 records from Rutgers University, Chrysler Herbarium - Mycology Collection. 22136 records from Weevil and Bark Beetle records via iRecord. 3 records from Three new species of the subgenus Ashima (Diptera: Drosophildae: Phortica) from southwestern China, with DNA barcoding information. 131 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 1737 records from Collembola of broadleaved forests along gradient of urbanization in Moscow. 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 113 records from Caracterización hidrogeológica para el diagnóstico ambiental de alternativas del proyecto hidroeléctrico San Bartolomé (ISAGEN y HMV).. 5 records from Nationalpark Harz Schul-AG Braunlage. 13450 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 4 records from A new species of the genus Lamellitettigodes (Orthoptera: Tetrigidae) from PR China, with taxonomic notes on the genus. 9 records from Dolichochorus Strobl 1904: a valid genus of Mesochorinae (Hymenoptera: Ichneumonidae: Mesochorinae). 125 records from My naturesounds - nature observations with sound recordings. 400 records from arthropods on Plantago lanceolata. 751 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 96 records from The species of the genus Diaclina Jacquelin du Val (Coleoptera: Tenebrionidae: Alphitobiini) from Sub-Saharan Africa. 10 records from A new genus of Tetracampidae (Hymenoptera) from South Africa. 7 records from Description Of A New Species Of Pterostichus Bonelli, P. barri, From The Appalachian Mountains (Coleoptera: Carabidae). 31 records from A new Subleuconycta (Lepidoptera: Noctuidae: Acronictinae) species from Taiwan. 1933 records from Carabidae of the European North-East of Russia. 10 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 6649 records from Invertebrate collection of University of Oulu Zoological Museum. 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 14 records from Four new species of Mileewini leafhoppers (Hemiptera: Cicadellidae: Mileewinae) from China, with a checklist to Chinese species. 1 records from University of New Mexico Herbarium. 17 records from Tejidos colectados en la expedición al municipio Cimitarra, Santander - Proyecto Santander BIO. 4616 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 13 records from MfN - Fossil vertebrates IV. 4 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 69 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 10 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 2 records from Nivå Bay species list, Zealand, Denmark. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 133 records from Contribution to the knowledge on the genus Barsine Walker, 1854 from mainland China and Indochina, with description of a new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 96290 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 9 records from A new species of Carpenter Moths (Lepidoptera, Cossidae) from Tarbagatai (NE Kazakhstan) and Altai (SW Siberia, Russia) Mountains. 2 records from Annotated checklist of the endemic Tetrapoda species of Iran. 9 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 358 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 14 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 377 records from Hydraenidae of Madagascar (Insecta: Coleoptera). 542 records from Arctic Ocean Diversity. 9 records from A contribution to taxonomy of the superfamily Grylloidea Laicharting from Yunnan, China (Orthoptera: Grylloidea). 7 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 7 records from Catch data from New Zealand research trawls since 2008. 13 records from The dacnusine genus Chorebus Haliday (Hymenoptera: Braconidae: Alysiinae) from China. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 5 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 2 records from New species of cynipid inquiline, Saphonecrus kuriphilusi (Hymenoptera: Cynipidae: Synergini), from Dryocosmus kuriphilus galls in Greece. 14 records from Five new species of the leafhopper genus Limassolla Dlabola (Hemiptera Cicadellidae: Typhlocybinae). 3 records from Nouvelles fourmis de Madagascar.. 6 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 115 records from Notes on taxonomy and distribution of some Palaearctic Ancylosis Zeller, 1839 (Lepidoptera: Pyralidae: Phycitinae). 7 records from Données de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS 2015 Chiroptères, Maculinea, Cistude d'Europe. 1 records from Données naturalistes d'Anaïs MAS. 21 records from Wassermann. 37 records from Palynological analysis of sediment core GeoB9508-5. 27 records from Données de la naturaliste Estelle Duchemann. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 29 records from Cryptic species in the nuisance midge Polypedilum nubifer (Skuse) (Diptera: Chironomidae) and the status of Tripedilum Kieffer. 11 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 35 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 151 records from Suivi temporel des Rhopalocères 2016. 569 records from Insectos del orden Trichoptera de la Sierra Tarahumara, Chihuahua, México. 2 records from COR herbarium - Universidade Federal de Mato Grosso do Sul / Campus Pantanal - Herbário Virtual Reflora. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 231 records from Ibaraki Nature Museum, Mollusk collection. 85 records from New findings of the butterfly Phengaris teleius at the border between Hungary and Serbia (Lepidoptera: Lycaenidae). 11 records from Revision of the bee genus Chlerogella (Hymenoptera, Halictidae), Part I: Central American species. 52 records from Review of the subgenus Tachycines (Gymnaeta) Adelung, 1902 (Orthoptera, Rhaphidophoridae, Aemodogryllinae, Aemodogryllini). 7 records from sediment metagenome Raw sequence reads. 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 228 records from Bishop's University Insect Collection (BUIC). 3 records from A new species of the simplex group of the genus Carpelimus Leach, 1819 (Coleoptera: Staphylinidae: Oxytelinae) from Thailand. 28777 records from Environment Agency England and Wales (2007) freshwater invertebrate species (single species families). 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 3 records from HURB - Herbário do Recôncavo da Bahia. 1 records from Sediment metagenome. 46 records from SEWBReC Myriapods, Isopods, and allied species (South East Wales). 144794 records from BioFokus. 1156 records from Anymals+plants - Citizen Science Data. 1563 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 4 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 2 records from A new species of Platypleura Amyot & Audinet-Serville, 1843 (Hemiptera: Cicadidae: Cicadinae) from the Eastern Ghats of Andhra Pradesh, India. 3 records from Description of a new Caliphaea species from Yunnan, China (Odonata: Calopterygidae). 2 records from A new species of the genus Eucyclodes (Lepidoptera, Geometridae, Geometrinae) from China. 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 167 records from Fossil (WSHN-FO). 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 118 records from Generic key and catalogue of Mymaridae (Hymenoptera) of Mexico. 17 records from Review of Smicromorpha Girault (Hymenoptera: Chalcididae) with description of a new species from India. 1824 records from Données naturalistes de Pascal ROUSSE. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 105 records from Vaste étude d'impact sur la biodiversité de la bassée commanditée par EPTB dans le cadre de réalisation de casiers anti crues. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 7 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 281 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 5 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 5 records from Description of a new species of Capederces (Coleoptera: Cerambycidae: Cerambycinae) from South Africa. 17 records from Two new species of the genus Oryctopterus (Orthoptera: Stenopelmatidae: Oryctopinae) from India, with some notes on biology. 29 records from A study on Roeslerstammiidae (Lepidoptera) in the Insect Collection of Nankai University (NKU), with descriptions of three new species. 17 records from Two new species of Hoplonannus (Heteroptera: Schizopteridae: Schizopterinae) from the Brazilian Amazon. 74870 records from Banc de dades de biodiversitat de Catalunya-ArtroCat. 1524 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 17 records from City of Edinburgh Natural Heritage Service - General Public Records.. 14 records from Laetosphecia, a new genus of clearwing moths from south-eastern China, with a brief review of the Sesiini from China (Lepidoptera, Sesiidae). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 12 records from Datos observacionales sobre biodiversidad Ministerio del Medio Ambiente 2015. 1 records from First record of the genus Yalvaciana (Tettigoniidae; Tettigoniinae; Platycleidini) with the description of a new species from India. 10 records from Revision of fossil Bibionidae (Insecta: Diptera) from the Miocene of Radoboj, Croatia. 1 records from Finnish Floristic Database (Finnish Museum of Natural History Collections). 123 records from Scolytodes Ferrari (Coleoptera, Scolytinae) from Ecuador: 40 new species. 9 records from Afrotropical flower flies (Diptera: Syrphidae). A new genus and species from Kenya, with a review of the melanostomine group of genera. 1 records from A new species of Phyllium (Phyllium) Illiger (Phasmida: Phylliidae) from Yap Island, Micronesia, representing a range expansion for the family. 17 records from New species and additional records of Cephalocousya and Drepasiagonusa from China and Russia (Coleoptera: Staphylinidae: Aleocharinae: Oxypodini). 28 records from New species and taxonomic notes for Cacostola Fairmaire and Germain, 1859 (Coleoptera: Cerambycidae: Lamiinae: Onciderini). 6 records from A new species of the genus Calambus C. G. Thomson, 1859 (Coleoptera: Elateridae: Dendrometrinae) from China, with notes on the other species of the genus of the East Palaearctic region. 15428 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 10 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 4 records from Two new species of Sochinsogonia (Hemiptera: Cicadellidae: Cicadellinae) from Philippines. 18 records from The genus Microptila Ris (Trichoptera, Hydroptilidae) in Japan. 11 records from A new species of Lycaena Fabricius, 1807 (Lepidoptera, Lycaenidae) from Mongolia with a review of genitalia characters of the related taxa. 144 records from The Xiphydria palaeanarctica group from Japan (Hymenoptera, Xiphydriidae). 54 records from The bee Ruizanthedella mutabilis Spinola (Hymenoptera: Halictidae): a very common but poorly known species studied using integrative taxonomy. 13 records from Mainufer. 9 records from A new apterous genus of Carventinae from Hainan, China (Hemiptera: Heteroptera: Aradidae). 2 records from Éthologie sonore et statut acoustique de quelques Cigales thaïlandaises, incluant la description de deux espèces nouvelles (Hemiptera: Auchenorhyncha *, Cicadoidea, Cicadidae). 2 records from A new species of the leafhopper genus Drabescus Stål (Hemiptera: Cicadellidae: Deltocephalinae) from China, with a checklist and key to species. 1 records from VFD-RP: Eifel: Orchideenweide Ankly. 1 records from Larval morphology of Plagiosterna adamsii (Baly) and P. aenea (Linnaeus) with resurrection of Gastrolinoides Chûjô & Kimoto and P. formosana (Bates) (Coleoptera: Chrysomelidae: Chrysomelinae). 763 records from Données naturalistes de Monsieur DAMOISEAU Sébastien. 3 records from One new species and one newly recorded species in the subgenus Myothorax Murray 1864 from China (Coleoptera: Nitidulidae: Carpophilinae: Carpophilus). 44 records from Molluscan specimens of Bihoro Museum. 42 records from A revision of Palaearctic and Oriental Scymbalium and Micrillus III. New species, new combinations, and additional records (Coleoptera: Staphylinidae: Paederinae). 9 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 5327 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 3 records from Données naturalistes de Stéphane ORIO. 59 records from Suivi botanique et entomologique pour la gestion de la portée de RTE sur l'emprise de la RNN de Bassée. 28 records from WildesMoor bei Schwabstedt. 62 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 20 records from Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 212 records from Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 15 records from Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus. 26 records from Persescaphium pari new genus and species, with an overview of Iranian Scaphidiinae (Coleoptera, Staphylinidae). 15 records from Revision of the genus Amazunculus Rafael (Diptera: Pipunculidae), with description of six new species. 2 records from Données naturalistes de ANDY PAPACOTSIA. 8 records from A taxonomic review of the genus Triscaedecia (Lepidoptera: Alucitidae) in the world fauna. 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 6 records from Status changes in some species of Leptohyphes Eaton (Leptohyphidae, Ephemeroptera). 11 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 187 records from A revision of the genus Eutetrapha Bates (Coleoptera: Cerambycidae: Lamiinae: Saperdini). 2 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 1 records from Notes on the tribe Tongini, with description of a new species of the genus Orthophana from northern Vietnam (Hemiptera: Fulgoroidea: Nogodinidae). 4 records from Description of new species of Ambrosiodmus Hopkins and Dryocoetoides Hopkins (Curculionidae: Scolytinae: Xyleborini) from Mexico. 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 1 records from A new species of Asphinctopone (Hymenoptera: Formicidae: Ponerinae) from Tanzania.. 363582 records from Monarch Watch. 21698 records from Collection Thysanoptera SMF. 9 records from Aurum, a new monotypic genus of Cetoniinae (Coleoptera: Scarabaeidae) endemic to Western Australia, Australia. 36 records from Review of Afrotropical species of Goetheana Girault (Hymenoptera: Eulophidae), with description of a new species. 2 records from New ichneumonids (Hymenoptera, Ichneumonidae) from the Eocene Tadushi Formation, Russian Far East. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 117 records from A review of the ant genus Myrmecorhynchus (Hymenoptera: Formicidae). 250 records from The large carrion beetles (Coleoptera: Silphidae) of Turkey: a review with a new species record. 1 records from Revision of the genus Tephrochlaena, with a key to genera of Palaearctic Heteromyzinae (Diptera: Heleomyzidae). 13 records from The Larvae of European Ascalaphidae (Neuroptera). 1945 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 547 records from The Sphecid wasps of the genus Cerceris LATREILLE, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from Subsaharan Africa and Madagascar, with description of five new species (Hymenoptera, Apoidea, Crabronidae). 4 records from Description of a new species and a new record of the genus Nola Leach, 1815 (Lepidoptera, Nolidae, Nolinae) from Tibet, China. 6 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 2 records from A new genus and new species of subfamily Trioxinae (Hymenoptera: Aphidiidae) from the Far East of Russia. 57 records from Données espèces - Expertise IQE 89. 988 records from Hoverflies (Syrphidae) of Ireland. 1 records from Inventory of plant species through Benin (West Africa). 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 5 records from Review of the genus Microcurgus Haupt, 1950 (Hymenoptera, Pompilidae) with description of a new species from Iran. 6 records from The bee genus Caenaugochlora (Hymenoptera, Apoidea) and its constituent subgenera, with new species of Caenaugochlora s. str. from Ecuador. 4 records from A new species of Ephoron Williamson, 1802 (Ephemeroptera: Polymitarcyidae) from Thailand. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 714 records from Revision of Australian species of the dung beetle genus Lepanus (Coleoptera: Scarabaeidae: Scarabaeinae): description of 10 new species from the L. australis, L. monteithi, and L. villosus species groups. 22 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 1071 records from International Fossil Shell Museum (NL) - Mollusca Collection. 7 records from Observations on the biology of Afrotropical Hesperiidae (Lepidoptera). Part 6. Hesperiinae incertae sedis: palm feeders. 132 records from Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 24 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 5 records from A new species of the Neotropical genus Beebeomyia (Diptera: Richardiidae) with observations of its biology on Dieffenbachia oerstedii (Araceae). 192 records from Traumatomutilla André miscellanea: Revision of the bellica, bifurca, diabolica, and vitelligera species groups, and a new group for the new species T. pilkingtoni Bartholomay and Williams (Hymenoptera: Mutillidae: Sphaeropthalminae: Dasymutillini). 1 records from Microbial community in PAH-contaminated riverine sediments. 17 records from Reconsideration of the genera Merogomphus Martin, 1904, and Anisogomphus Selys, 1857, including erection of a new genus, with a new species and discussion of additional specimens from Cambodia. 2503 records from Rådgivende Biologer. 13 records from Four new species of Pomphopsilla Jałoszyński in Rwanda, Burundi and DR Congo (Coleoptera: Staphylinidae: Scydmaeninae). 10798 records from Heteroptera collections of SW Finland. 1 records from Cabamofa orientalis sp. nov. from Thailand, congeneric with C. mira Jaschhof from Costa Rica (Diptera: Bibionomorpha: Sciaroidea incertae sedis). 6 records from Moribaetis brachiostrinus (Ephemeroptera: Baetidae), a new species of mayfly from Costa Rica. 345 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 149 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 2 records from Leptagrion itabaiana sp. nov. (Odonata: Coenagrionidae) from Serra de Itabaiana National Park, Sergipe state, Northeastern Brazil. 2 records from A new species of Miobantia Giglio-Tos, 1917 with a novel morphological feature (Mantodea: Thespidae: Miobantiinae). 3558 records from Regroupement de données Odonates. 8 records from A New Species Of Perlesta (Plecoptera: Perlidae) From New York. 20 records from Mollusca Collection of Saitama Museum of Natural History. 1 records from Description of Gondwanoscurus curleri sp. nov. from the West Usambara Mts, Tanzania (Diptera: Psychodidae). 31 records from Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia. 12 records from A new species of Conopsia Strand, 1913 (Lepidoptera: Sesiidae: Tinthiinae) from West Africa. 9 records from New distribution records of the genus Saga Charpentier, 1825 (Orthoptera Tettigoniidae: Saginae) from Iraq. 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 23 records from Kiwisaldula (Hemiptera: Heteroptera: Saldidae) from the South Island of New Zealand: new species and identification key. 48 records from New species and records of Entomobryidae and Orchesellidae (Collembola) from the East Caucasus (Russia). 12 records from Lance lacewings of the world (Neuroptera: Archeosmylidae, Osmylidae, Saucrosmylidae): review of living and fossil genera. 76 records from Inventaire hivernal des nids de frelon asiatique. 2 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 7 records from A new species of Catomus Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from the Aeolian archipelago (Sicily, Italy). 15 records from Genus Cathyalia Ragonot, 1888 (Lepidoptera: Pyralidae), new record phycitine to China. 4 records from Two new species of Bucculatrix Zeller (Lepidoptera: Bucculatricidae) from China. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 174 records from Taxonomic revision of Stagmatoptera Burmeister, 1838 (Mantodea: Mantidae, Stagmatopterinae). 2 records from Colletes alborzensis nov. sp., a new bee species from Iran (Hymenoptera, Colletidae). 4 records from A needle in a haystack: the new genus Bernadottea (Diptera: Cecidomyiidae, Winnertziinae) with four new species in the Old World. 5 records from Discovery of a third species of Lamproptera Gray, 1832 (Lepidoptera: Papilionidae). 1 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 3 records from Cyana fossi, a new species from Vietnam (Lepidoptera: Erebidae: Arctiinae Lithosiini). 3 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 30 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 5 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 20 records from Review of the leafhopper tribe Macrostelini Kirkaldy (Cicadellidae: Deltocephalinae) in Pakistan with description of a new species. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 43 records from Records Of Anacroneuria (Plecoptera: Perlidae) From Bolivia And Paraguay With Descriptions Of Three New Species. 3 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 9 records from Aktion Wiese und Wegrain Gitzenheide. 6 records from Two new species of Coeliccia Kirby from Yunnan, China (Odonata: Zygoptera Platycnemididae). 14 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 5 records from Taxonomic review of the ant genus Dilobocondyla from China (Hymenoptera: Formicidae), with a revised key to the known species. 7 records from Örtzemündung (Stedden). 760 records from Invertebrates compiled by W.Block. 10 records from Bolzplatz. 5699 records from Insect (HUNM-IN). 5 records from Données naturalistes de Monsieur VILAIN Frederic. 15 records from Descriptions of two new genera of Maruinini (Diptera, Psychodidae, Psychodinae) from the Mitaraka range of French Guiana. 60221 records from National Stag Beetle Surveys (Great Stag Hunts). 36 records from Marine Offshore Seabed Survey data held by JNCC. 16 records from Abundance of the benthic infauna of the North Sea sampled during Victor Hensen cruise VH1486. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 1211 records from Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 15 records from Pupae of the Nearctic species of Culicoides Latreille subgenus Monoculicoides Khalaf (Diptera: Ceratopogonidae). 1288 records from Barcant Butterfly Collection - Nymphalidae. 11704 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Entomologica). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Description of two new species and phylogenetic reassessment of Perelle
Keywords: GBIF; biodiversity; species occurrences